Photocatalytic barrier composite film for fresh keeping of fruits and vegetables and preparation method of photocatalytic barrier composite film
Through the use of photocatalytic barrier composite film, the problem of insufficient gas barrier performance of traditional plastic wrap is solved, and more efficient fruit and vegetable preservation is achieved, extending the shelf life and reducing food waste.
Patent Information
- Application Number
- CN202510181110.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The gas barrier properties of traditional fruit and vegetable plastic wrap are not ideal enough, and the transmittance of oxygen and carbon dioxide cannot be accurately controlled, resulting in accelerated respiration of fruit and vegetable and odor generated by anaerobic respiration, affecting quality.
A photocatalytic barrier composite film is used, which modified nanocellulose by sulfonating and quaternization, combined with organic intercalation, and is supported by titanium dioxide and zinc oxide, and degraded harmful microorganisms and ethylene by photocatalytic action.
It significantly improves the shelf life of fruits and vegetables, reduces food waste and losses, and achieves a more efficient and lasting freshness effect, reducing its impact on the environment.
Smart Images

Figure CN119639048A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fruit and vegetable preservation, and relates to a photocatalytic barrier composite film for fruit and vegetable preservation and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, the requirements for the freshness and quality of fruits and vegetables are becoming increasingly stringent. After being picked, fruits and vegetables are still living organisms and will continue to breathe and metabolize physiologically, which will cause them to gradually lose water, lose nutrients, taste worse, and even rot and deteriorate. Therefore, effective preservation technology is crucial to maintaining the quality of fruits and vegetables, extending their shelf life, and reducing post-harvest losses.
[0003] As a widely used preservation method, plastic wrap plays an important role in the preservation of fruits and vegetables. Traditional plastic wrap for fruits and vegetables is mainly made of plastic films such as polyethylene (PE) and polyvinyl chloride (PVC). These plastic wraps have certain barrier properties, which can slow down the gas exchange between fruits and vegetables and the external environment to a certain extent, inhibit the respiration of fruits and vegetables, and thus extend the shelf life of fruits and vegetables. At the same time, they are low in cost and easy to process and shape, and have been widely used in the market.
[0004] However, there are many problems with traditional cling film in practical applications. From the perspective of preservation effect, its preservation ability is limited and cannot fully meet the needs of modern consumers for long-term preservation of fruits and vegetables. The gas barrier performance of traditional cling film is not ideal. Although it can adjust the gas environment around fruits and vegetables to a certain extent, the control of the permeability of oxygen and carbon dioxide is not accurate enough. Too much oxygen entering will accelerate the respiration and oxidation process of fruits and vegetables, resulting in rapid consumption of nutrients, while excessive accumulation of carbon dioxide will cause anaerobic respiration and produce odorous substances such as alcohol, affecting the flavor and quality of fruits and vegetables. In addition, the barrier effect of traditional cling film on moisture is also insufficient. Fruits and vegetables will continue to lose water during storage, resulting in weight loss, skin shrinkage, and reduced commodity value.
[0005] In order to solve the above problems, researchers are constantly exploring new materials and technologies for fruit and vegetable preservation. As an emerging green technology, photocatalytic technology has shown great potential in the fields of environmental purification, antibacterial disinfection, etc. Introducing photocatalytic technology into the field of fruit and vegetable preservation and preparing barrier films with photocatalytic functions provide new ideas and methods for fruit and vegetable preservation.
[0006] Under the action of photocatalysis, the photocatalytic barrier composite film can effectively degrade harmful microorganisms on the surface of fruits and vegetables. When irradiated by light of a specific wavelength, the photocatalytic material will produce electron-hole pairs. These electrons and holes have strong redox ability and can react with oxygen and water in the air to generate active species such as hydroxyl radicals and superoxide anion radicals with strong oxidizing properties. These active species can destroy the cell membranes, proteins, nucleic acids and other biological macromolecules of microorganisms, thereby achieving the effect of sterilization and disinfection, and reducing the decay and deterioration of fruits and vegetables caused by microbial infection.
[0007] Photocatalytic barrier composite films can also efficiently decompose ethylene and other ripening gases produced during the preservation of fruits and vegetables. Ethylene is a plant hormone that plays a key regulatory role in the ripening and aging of fruits and vegetables. During the preservation of fruits and vegetables, ethylene is continuously produced as fruits and vegetables respire, accelerating the ripening and aging process of fruits and vegetables. Photocatalytic materials can use photogenerated carriers to decompose ethylene into harmless substances such as carbon dioxide and water, reduce the concentration of ethylene in the environment, thereby delaying the ripening and aging of fruits and vegetables and maintaining the freshness and quality of fruits and vegetables.
[0008] This photocatalytic barrier composite film not only has good gas and moisture barrier properties, but can also use photocatalysis to degrade harmful microorganisms and gases such as ethylene on the surface of fruits and vegetables, thereby achieving a more efficient and lasting preservation effect while reducing the impact on the environment. It has broad application prospects. Summary of the invention
[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocatalytic barrier composite film for preserving fruits and vegetables and a preparation method thereof. The composite film prepared by the present invention has excellent photocatalytic performance, antibacterial performance, barrier performance and mechanical properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables, the preparation method comprising:
[0012] (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose;
[0013] (II) using hexadecyltrimethylammonium bromide and caprolactam to carry out organic intercalation modification on montmorillonite to obtain intercalated montmorillonite; then, using a silane coupling agent to carry out hydrophobic modification on the intercalated montmorillonite to obtain a composite modified montmorillonite;
[0014] (III) uniformly mixing tetrabutyl titanate, triethanolamine and anhydrous ethanol to obtain a titanium precursor solution; uniformly mixing zinc acetate, urea, sodium citrate and deionized water to obtain a zinc precursor solution; uniformly mixing the composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water to obtain a montmorillonite dispersion; under stirring and heating conditions, sequentially dropping the titanium precursor solution and the zinc precursor solution into the montmorillonite dispersion to obtain a composite sol; sequentially aging, centrifuging, washing, drying and calcining the composite sol to obtain a loaded modified montmorillonite;
[0015] (IV) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the loaded modified montmorillonite obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the photocatalytic barrier composite film for preserving fruits and vegetables.
[0016] The photocatalytic barrier composite film prepared by the present invention has excellent photocatalytic performance, antibacterial performance, barrier performance and mechanical properties. In the preparation process, the present invention firstly treats the nanocellulose by sulfonation and quaternization modification, thereby improving its dispersibility and compatibility in the polymer matrix, and then enhancing the mechanical properties and barrier properties of the composite film. Subsequently, the montmorillonite is organically intercalated with hexadecyltrimethylammonium bromide and caprolactam to increase the interlayer spacing of the montmorillonite, and then the intercalated montmorillonite is hydrophobically modified by a silane coupling agent to obtain a composite modified montmorillonite. Finally, titanium dioxide and zinc oxide are loaded on the interlayer and surface of the composite modified montmorillonite by a sol-gel method, and the different energy band structures of titanium dioxide and zinc oxide are used to give the loaded modified montmorillonite excellent photocatalytic ability, so that the final composite film can use light of different wavelengths to produce more active oxygen species, efficiently decompose ripening gases such as ethylene, and inhibit the ripening and aging of fruits and vegetables.
[0017] The present invention combines the high specific surface area and high strength of quaternary ammonium sulfonated nanocellulose with the layered structure and photocatalytic performance of the loaded modified montmorillonite, thereby enhancing the mechanical properties of the composite film while greatly improving its barrier properties, and can form a tortuous gas permeation path in the polymer matrix, thereby delaying the respiration and water loss of fruits and vegetables; at the same time, the quaternary ammonium sulfonated nanocellulose itself is antibacterial, and the active oxygen species generated by the loaded modified montmorillonite through photocatalysis can destroy bacterial cell walls and cell membranes, and the synergistic effect of the two can significantly enhance the antibacterial properties of the composite film, reduce microbial contamination, and ensure the freshness of fruits and vegetables.
[0018] Compared with traditional chemical preservation products, the composite film prepared by the present invention utilizes physical barrier effect and photocatalysis to achieve the preservation effect, does not rely on chemical reagents, and can be used to wrap fruits and vegetables with the composite film. No harmful substances will remain on the surface or inside of the fruits and vegetables, and no harm will be caused to human health and the environment. It meets the requirements of green environmental protection and food safety, and can provide consumers with safer and healthier fruit and vegetable products.
[0019] Nanocellulose is one of the most abundant natural polymers. It has the advantages of wide source, renewable, biodegradable, good biocompatibility and green environmental protection. In addition, it has excellent mechanical properties, high specific surface area, low density and good thermal stability. It is an excellent nano-reinforced filler. The tensile strength, elastic modulus, thermal stability and barrier properties of the composite film can be significantly improved by adding nanocellulose to the polymer matrix. However, there are a large number of hydroxyl functional groups on the surface of nanocellulose, which hinders its compatibility and dispersibility in the polymer matrix and limits the further enhancement of the performance of the composite film. Therefore, it is necessary to hydrophobically modify nanocellulose and reduce its hydrophilicity, so as to improve the compatibility and dispersibility of nanocellulose in the polymer matrix. In addition, in order to give the composite film excellent antibacterial properties, it is necessary to consider the compatibility of the antibacterial agent in the composite material system to avoid the negative impact of the addition of the antibacterial agent on the performance of the composite film.
[0020] In order to solve the problem that the hydrophilic nanocellulose is dispersible in the hydrophobic polymer matrix and the nanocellulose lacks antimicrobial activity, the present invention adopts sulfonation and quaternary ammonium salt adsorption combined modification to treat the nanocellulose, so that the surface properties of the nanocellulose are optimized, not only reducing the hydrophilicity of the nanocellulose, improving its compatibility and dispersibility with the polymer matrix, but also introducing more polar functional groups, which is conducive to forming a stronger interface interaction. At the same time, the modified nanocellulose also gives the composite film excellent antimicrobial properties and mechanical properties, and the quaternary ammonium sulfonated nanocellulose forms a continuous network structure in the composite film, effectively improving the tensile strength and toughness of the composite film.
[0021] Among the numerous organic antimicrobial modifiers, quaternary ammonium antimicrobial agents have the advantages of broad-spectrum antimicrobial activity, low toxicity, low price, and good environmental stability. The bactericidal mechanism is as follows: quaternary ammonium cations adsorb negatively charged bacterial cell membranes on the surface through electrostatic action, and then the long alkane chains of quaternary ammonium salts enter the phospholipid bilayer of the cell membrane, interfering with the normal metabolism of bacterial cells, and ultimately leading to bacterial cell lysis to achieve bactericidal and antibacterial effects. Due to the electrostatic adsorption mechanism of quaternary ammonium salts in the antibacterial process, they can widely act on the negatively charged bacterial surface rather than specifically bind to kill bacteria, and thus can effectively avoid the risk of increased bacterial resistance.
[0022] Since polymer quaternary ammonium salts have more action sites and higher charge density, they are more conducive to the electrostatic adsorption effect, and the adsorption effect between bacteria is faster and stronger; however, too large a molecular weight will also affect the contact of quaternary ammonium salt molecules with the bacterial surface to play a role, which will lead to a weakening of antibacterial activity. The present invention uses octadecyl trimethyl ammonium chloride as an organic antibacterial agent, and uses physical electrostatic adsorption to load octadecyl trimethyl ammonium chloride onto nanocellulose, thereby satisfying the dual modification purposes of hydrophobic modification and antibacterial modification of nanocellulose. However, the loading amount of nanocellulose on octadecyl trimethyl ammonium chloride depends on the anion content present on its surface. In order to increase the loading amount of octadecyl trimethyl ammonium chloride, the present invention first sulfonates the nanocellulose by 1,3-propane sultone. The sulfonation modification can provide abundant and stable anion sites for the surface of nanocellulose, which is conducive to improving the adsorption of nanocellulose on octadecyl trimethyl ammonium chloride.
[0023] As a natural layered silicate mineral, montmorillonite has closely stacked layers in its original state, with a small interlayer spacing, and cations are tightly bound between the layers. Such a structure is not conducive to the subsequent loading and uniform dispersion of titanium dioxide and zinc oxide. To this end, the present invention uses hexadecyltrimethylammonium bromide and caprolactam to perform composite intercalation modification on montmorillonite, and after ion exchange between the organic cations of hexadecyltrimethylammonium bromide and the inorganic cations between the montmorillonite layers, the cations are partially attached to the montmorillonite layers, and the organic parts remain between the layers, thereby increasing the interlayer spacing of the montmorillonite, making the structure more loose, the porosity higher, and partial layer peeling.
[0024] However, the cost of modifying montmorillonite with hexadecyltrimethylammonium bromide alone is not only high, but also the modified montmorillonite has poor compatibility with titanium precursor solution and zinc precursor solution, so it is difficult to form an intercalation structure with titanium dioxide and zinc oxide. For this reason, on the basis of using hexadecyltrimethylammonium bromide for organic intercalation modification, the present invention adds caprolactam to carry out composite modification of montmorillonite. After the hexadecyltrimethylammonium bromide / caprolactam composite intercalation modification, the subsequent loading stability of titanium dioxide and zinc oxide can be significantly improved. This is because, on the one hand, after the hexadecyltrimethylammonium bromide and montmorillonite are subjected to cation exchange, the interlayer spacing of the montmorillonite is expanded to a certain extent, providing sufficient adsorption space for the subsequent entry of caprolactam; at the same time, through the hexadecyltrimethylammonium bromide intercalation After the layer modification, the interlayer microenvironment of montmorillonite changes from hydrophilic to lipophilic, which is conducive to the adsorption of caprolactam into the interlayer of montmorillonite. The C=O functional group of caprolactam adsorbed into the interlayer of montmorillonite easily forms hydrogen bonds with the -OH functional group of bentonite interlayer, thereby introducing caprolactam molecules into the interlayer of montmorillonite, further expanding the interlayer spacing of montmorillonite. The increased interlayer spacing makes the active sites between montmorillonite sheets more easily exposed, increasing the chance of chemical reaction with the titanium precursor solution and the zinc precursor solution, thereby improving the loading stability of titanium dioxide and zinc oxide. On the other hand, the insertion of hexadecyltrimethylammonium bromide and caprolactam changed the electron cloud distribution of the montmorillonite sheet, enhancing its chemical activity. During the loading process, this high reactivity accelerated the reaction rate of the titanium precursor solution and the zinc precursor solution with montmorillonite, and promoted the loading process of titanium dioxide and zinc oxide on the montmorillonite sheet; at the same time, the high reactivity helps to complete the loading reaction of titanium dioxide and zinc oxide at a lower temperature and in a shorter time, reducing the adverse effects that may be caused by high temperature and long-term reaction, such as the agglomeration of titanium dioxide and zinc oxide particles and the destruction of the crystal structure, thereby ensuring the photocatalytic performance of the loaded material.
[0025] The organic intercalation modification of montmorillonite using hexadecyltrimethylammonium bromide and caprolactam is achieved by entering the interlayers of montmorillonite through ion exchange and chemical bonding. However, this modification method can only modify the interlayers of montmorillonite, which can increase the interlayer spacing of montmorillonite and provide a certain space for the loading of titanium dioxide and zinc oxide. However, the surface modification effect of montmorillonite only through intercalation modification treatment is insufficient, so it is impossible to significantly improve the surface hydrophobicity of montmorillonite, thereby affecting its compatibility with the polymer matrix. To this end, after the intercalation modification of montmorillonite, the present invention further uses a silane coupling agent to perform hydrophobic modification on the intercalation montmorillonite. The silane coupling agent is a substance having two functional groups of different chemical properties, a non-hydrolyzable functional group and a hydrolyzable functional group. The silanol generated by hydrolysis can react with the hydroxyl group on the surface of the intercalation montmorillonite to be grafted onto the surface of the intercalation montmorillonite. At the same time, the silanol grafted onto the surface of the intercalation montmorillonite associates with each other to form a hydrophobic film with a network structure and covers the surface of the intercalation montmorillonite. The composite modified montmorillonite obtained after modification by the silane coupling agent changes from hydrophilic to hydrophilic. It is hydrophobic and has improved compatibility with titanium precursor solution and zinc precursor solution. Under heating and stirring conditions, titanium precursor solution and zinc precursor solution can be more tightly adsorbed on the montmorillonite layer, and can react better with the montmorillonite layer to form a more stable chemical bond, so that titanium dioxide and zinc oxide are firmly loaded on the montmorillonite layer. This strong interaction not only improves the loading stability of titanium dioxide and zinc oxide, but also affects the crystal growth and structure of titanium dioxide and zinc oxide to a certain extent, which is conducive to the formation of a composite structure with good photocatalytic properties.
[0026] The present invention uses tetrabutyl titanate as a titanium source, and tetrabutyl titanate, triethanolamine and anhydrous ethanol are uniformly mixed to obtain a titanium precursor solution, and the titanium precursor solution is dripped into a water-containing montmorillonite dispersion. Under hydrothermal stirring conditions, the hydrolysis of tetrabutyl titanate occurs first, and the butoxy group in the tetrabutyl titanate molecule is gradually replaced by a hydroxyl group under the action of water. This is because the hydrothermal environment provides abundant water molecules, and the oxygen atoms in the water molecules have lone pairs of electrons, which can attack the electropositive titanium atoms in the tetrabutyl titanate molecules, so that the butoxy group leaves and forms an intermediate product titanium alkoxide. As the hydrolysis reaction proceeds, a polycondensation reaction occurs between the generated titanium alkoxides, and multiple titanium alkoxide molecules form oligomers containing Ti-O-Ti bonds through dehydration condensation or dealcoholization condensation, and these oligomers are further interconnected and grown to gradually form titanium dioxide particles with a certain structure. In the hydrothermal system, the high temperature environment accelerates the movement and reaction rate of the molecules, making the polycondensation reaction easier to proceed, which is conducive to the formation of titanium dioxide particles with uniform size and good crystallinity. At the same time, triethanolamine plays a complexing and stabilizing role in the reaction. It can form a complex with titanium ions, control the hydrolysis and condensation rates of titanium ions, and avoid particle agglomeration caused by too rapid reaction, thereby ensuring that the generated titanium dioxide particles have good dispersibility.
[0027] The present invention uses zinc acetate as a zinc source, mixes zinc acetate, urea, sodium citrate and deionized water to obtain a zinc precursor solution, and then drips the solution into a montmorillonite dispersion after all the titanium precursor solution is dripped in. Under hydrothermal stirring conditions, urea is hydrolyzed to generate ammonium carbonate and ammonia, and the ammonium carbonate is further decomposed to generate carbonate ions and ammonium ions. The zinc ions in the solution are combined with the carbonate ions to generate a zinc carbonate intermediate product. As the hydrothermal reaction proceeds, the zinc carbonate decomposes and recrystallizes under the action of high temperature and sodium citrate. As a complexing agent, sodium citrate can form a stable complex with zinc ions, adjust the concentration and activity of zinc ions in the solution, and control the decomposition rate of zinc carbonate and the crystallization process of zinc oxide. Zinc carbonate decomposes to generate zinc oxide and carbon dioxide, and the newly formed zinc oxide gradually crystallizes and grows in a hydrothermal environment to form zinc oxide particles with a specific crystal structure and morphology. Due to the controllability of the hydrothermal conditions, the size, shape and crystallinity of the zinc oxide particles can be accurately regulated, thereby optimizing its photocatalytic performance.
[0028] Titanium dioxide and zinc oxide loaded on the composite modified montmorillonite can improve the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the composite film from multiple dimensions by virtue of their own characteristics and synergistic effect, effectively inhibit the growth of harmful microorganisms on the surface of fruits and vegetables, and extend the shelf life of fruits and vegetables. Specifically:
[0029] In terms of photocatalytic performance, zinc oxide and titanium dioxide have different energy band structures. The band gap width of titanium dioxide is about 3.0-3.2eV, and the band gap width of zinc oxide is about 3.37eV. When irradiated with light, photons with energy greater than their band gap width can excite titanium dioxide and zinc oxide to produce electron-hole pairs. Due to the difference in the energy band structures of the two, in the composite system composed of titanium dioxide and zinc oxide, electrons and holes will undergo a directionally transferred from the conduction band of titanium dioxide to the conduction band of zinc oxide, and holes will transfer from the valence band of zinc oxide to the valence band of titanium dioxide. This directional transfer of electrons and holes effectively prolongs the lifetime of carriers, allowing more electrons and holes to participate in the photocatalytic reaction and produce more superoxide anion radicals and hydroxyl radicals. Since fruits and vegetables release ripening gases such as ethylene during storage, accelerating their own ripening and aging, the superoxide anion free radicals and hydroxyl free radicals produced by titanium dioxide and zinc oxide under photocatalysis have extremely strong oxidizing properties and can efficiently oxidize and decompose organic ripening gases such as ethylene, converting them into harmless substances such as carbon dioxide and water, thereby delaying the ripening process of fruits and vegetables and extending the shelf life. At the same time, the photocatalytic system formed by the synergistic effect of the two also broadens the absorption range of the composite film to light of different wavelengths. It can not only utilize ultraviolet rays, but also respond to part of visible light. Photocatalytic reactions can be achieved under different lighting conditions, thereby stimulating titanium dioxide and zinc oxide to produce photocatalytic antibacterial activity. Whether in a storage environment with natural light or in an environment such as supermarket shelves with artificial light sources, the photocatalytic performance can be effectively exerted, enhancing the adaptability of the composite film to different environments.
[0030] In terms of antibacterial properties, titanium dioxide and zinc oxide can generate active oxygen species through photocatalysis. When irradiated with light with energy greater than their bandgap, titanium dioxide and zinc oxide will generate electron-hole pairs, in which electrons are reducing and holes are oxidizing. Photogenerated electrons can reduce adsorbed oxygen to superoxide anion radicals (·O2 - ), photogenerated holes can oxidize water into hydroxyl radicals (·OH). Both superoxide anion radicals and hydroxyl radicals have extremely strong oxidizing properties and are key factors in antibacterial properties. For common harmful microorganisms of fruits and vegetables such as Escherichia coli and Staphylococcus aureus, their cell walls and cell membranes are mainly composed of polysaccharides, proteins and other substances. Superoxide anion radicals can attack the unsaturated bonds in the cell walls and cell membranes, triggering lipid peroxidation reactions, leading to the destruction of the integrity of the cell membrane and leakage of cell contents. Hydroxyl radicals can directly oxidize biological macromolecules such as proteins and nucleic acids, causing the bacteria to lose their physiological functions, thereby achieving the purpose of sterilization.
[0031] In terms of barrier properties, the penetration of gases such as O2 and CO2 will affect the respiration of fruits and vegetables, thereby affecting the preservation of fruits and vegetables. The photogenerated carriers produced by the synergistic reaction of titanium dioxide and zinc oxide can react with oxygen in the air to generate superoxide free radicals (·O2 - ) and other active oxygen species. These active oxygen species can react with organic pollutants adsorbed on the surface of the composite film to decompose them into small molecules, thereby cleaning the surface of the composite film. This process effectively reduces the adsorption sites of gas molecules on the surface of the composite film, reduces the amount of gas adsorption, and inhibits gas diffusion. In addition, the photogenerated carriers can also interact with some functional groups inside the composite film, so that the interaction between the polylactic acid molecular chains is enhanced, forming a tighter network structure. When gas molecules pass through the composite film, they need to overcome greater resistance, which increases the tortuosity of the gas diffusion path, thereby significantly reducing the gas permeability and improving the barrier properties of the composite film.
[0032] In terms of mechanical properties, titanium dioxide has high hardness and modulus, and plays the role of reinforcing phase in the composite film. When the composite film is subjected to external force, titanium dioxide can bear part of the load and limit the deformation of the polymer matrix, thereby improving the tensile strength and elastic modulus of the composite film. Zinc oxide also has a certain rigidity, and its presence further enhances the ability of the composite film to resist deformation. At the same time, zinc oxide can also improve the crystallization properties of the composite film to a certain extent, making the arrangement of the polylactic acid molecular chains more regular, which is conducive to improving the cohesive energy of the composite film and thus enhancing the mechanical properties of the composite film. In addition, the active oxygen species produced by the photocatalytic reaction of titanium dioxide and zinc oxide can interact with the polymer matrix, form new chemical bonds between the polylactic acid molecular chains, enhance the interaction force between the polylactic acid molecular chains, and produce a similar "cross-linking" effect, making the network structure of the composite film more stable. When the composite film is subjected to external force, this stable network structure can more effectively disperse stress and avoid stress concentration leading to rupture of the composite film.
[0033] As a preferred technical solution of the present invention, in step (I), the sulfonated nanocellulose is prepared by the following method:
[0034] The nanocellulose powder is added into a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added into the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, and a hydrochloric acid solution is dripped into the reaction product to adjust its pH value, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose.
[0035] In some optional examples, the mass fraction of the sodium hydroxide solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the ratio of the nanocellulose powder to the sodium hydroxide solution is 1g:(50~60)mL, for example, it can be 1g:50mL, 1g:51mL, 1g:52mL, 1g:53mL, 1g:54mL, 1g:55mL, 1g:56mL, 1g:57mL, 1g:58mL, 1g:59mL or 1g:60mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional examples, the heating temperature during mixing and stirring of the nanocellulose dispersion is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide.
[0042] In some optional examples, the mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%, for example, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14~0.15), for example, it can be 1:0.14, 1:0.141, 1:0.142, 1:0.143, 1:0.144, 1:0.145, 1:0.146, 1:0.147, 1:0.148, 1:0.149 or 1:0.15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] The present invention particularly limits the mass ratio of nanocellulose powder to 1,3-propane sultone in the nanocellulose suspension to 1:(0.14-0.15). When the amount of 1,3-propane sultone used is lower than the lower limit of the range defined by the present invention, the number of sulfonic acid functional groups on the surface of the nanocellulose is too small, and the sulfonation modification is insufficient, thereby affecting the number of anion sites on the surface of the nanocellulose, resulting in a decrease in its adsorption capacity for octadecyltrimethylammonium chloride; in addition, the sulfonic acid functional groups serve as molecular bridges connecting the nanocellulose and octadecyltrimethylammonium chloride, and their insufficient number will directly affect the effect of quaternary ammonium modification, resulting in uneven distribution of octadecyltrimethylammonium chloride on the surface of the nanocellulose and a decrease in the grafting rate, which ultimately affects the antibacterial and mechanical properties of the quaternary ammonium sulfonated nanocellulose.
[0045] When the amount of 1,3-propane sultone exceeds the upper limit of the range defined by the present invention, it will cause excessive sulfonation of nanocellulose, causing significant changes in the chemical structure and physical properties of sulfonated nanocellulose, and the chain structure of sulfonated nanocellulose will break due to excessive reaction, resulting in a decrease in its strength, rigidity and stability. In addition, excessive sulfonation will also affect the subsequent quaternization modification effect, because, on the one hand, the sulfonic acid functional groups on the surface of sulfonated nanocellulose are limited in number as adsorption sites, and when the amount of 1,3-propane sultone is increased, although more sulfonic acid functional groups are introduced, the excessive amount of 1,3-propane sultone will lead to saturation of adsorption sites, and the part exceeding the carrying capacity of the surface of sulfonated nanocellulose will not be able to effectively participate in the subsequent quaternization reaction. On the other hand, during the quaternization process, octadecyltrimethylammonium chloride needs to be adsorbed on the sulfonic acid functional groups on the surface of sulfonated nanocellulose. When the dosage of 1,3-propane sultone is too high, it will lead to uneven distribution of sulfonic acid functional groups, which will in turn cause uneven distribution of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose, affecting the performance of the final product.
[0046] In some optional examples, the mixing and stirring time of the nanocellulose suspension and 1,3-propane sultone is 5 to 6 hours, for example, it can be 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the heating temperature when the nanocellulose suspension is mixed and stirred with 1,3-propane sultone is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional instances, the mass fraction of the hydrochloric acid solution is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional embodiments, hydrochloric acid solution is added dropwise to the reaction product to adjust its pH value to 1-2, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the dialysis time is 2 to 3 days.
[0052] In some optional embodiments, the freeze-drying temperature is -60~-70°C, for example, it can be -60°C, -61°C, -62°C, -63°C, -64°C, -65°C, -66°C, -67°C, -68°C, -69°C or -70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional embodiments, the freeze-drying time is 6 to 12 hours, for example, it can be 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10.0 h, 10.5 h, 11.0 h, 11.5 h or 12.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] As a preferred technical solution of the present invention, in step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method:
[0055] The sulfonated nanocellulose is added to triethylamine to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, and then octadecyltrimethylammonium chloride is added to the sulfonated nanocellulose suspension, mixed and stirred and heated for a period of time, and then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose.
[0056] The presence of triethylamine can improve the disorder of sulfonated nanocellulose and reduce the possibility of hydrogen bond formation and cross-linking, so that the sulfonated nanocellulose maintains a larger specific surface area, which is beneficial to the quaternary ammonium cationic modification reaction of the sulfonated nanocellulose. At the same time, the use of triethylamine can destroy the crystal structure of the sulfonated nanocellulose to a large extent, so that the quaternary ammonium modification reaction can be carried out more fully.
[0057] In some optional examples, the ratio of the sulfonated nanocellulose to triethylamine is 1g:(30~40)mL, for example, it can be 1g:30mL, 1g:31mL, 1g:32mL, 1g:33mL, 1g:34mL, 1g:35mL, 1g:36mL, 1g:37mL, 1g:38mL, 1g:39mL or 1g:40mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and triethylamine is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the ultrasonic dispersion time of the sulfonated nanocellulose and triethylamine is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional examples, the concentration of the alkali solution is 0.5~1.5mol / L, for example, it can be 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L or 1.5mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional embodiments, an alkali solution is added to the sulfonated nanocellulose suspension to adjust its pH value to 9-10, for example, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2~0.3), for example, it can be 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29 or 1:0.3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] The present invention particularly limits the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension to 1:(0.2-0.3). When the amount of octadecyltrimethylammonium chloride used is lower than the lower limit of the range defined by the present invention, the coverage of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose is insufficient. The antibacterial effect of octadecyltrimethylammonium chloride mainly depends on the interaction between its positive charge and the negative charge of the bacterial cell membrane, thereby destroying the integrity of the bacterial cell membrane. If the coverage of octadecyltrimethylammonium chloride is insufficient, the chance of octadecyltrimethylammonium chloride contacting with the bacterial cell membrane is reduced, resulting in decreased antibacterial performance of the product. In addition, as a cationic surfactant, the long-chain alkyl part of octadecyltrimethylammonium chloride has significant hydrophobic properties. When octadecyltrimethylammonium chloride is combined with sulfonated nanocellulose, the hydrophobic alkyl chains of the quaternary ammonium salt tend to be arranged in a direction away from water molecules, thereby forming a hydrophobic barrier on the surface of nanocellulose. This barrier can effectively prevent the penetration of water molecules and improve the hydrophobic properties of the material. When the amount of octadecyltrimethylammonium chloride is too small, the number of hydrophobic alkyl chains is limited and a complete hydrophobic barrier cannot be formed, resulting in insufficient hydrophobicity of the product, which in turn affects its compatibility and dispersibility with the polymer matrix.
[0064] Increasing the amount of octadecyltrimethylammonium chloride can increase the positive charge density on the surface of sulfonated nanocellulose, thereby enhancing the antibacterial properties of the product. However, when the amount of octadecyltrimethylammonium chloride exceeds the upper limit of the range defined in the present invention, the hydrophobic modification of the surface of the sulfonated nanocellulose is close to saturation. Continuing to increase the amount of octadecyltrimethylammonium chloride cannot further increase the number of hydrophobic alkyl chains. Instead, it may cause the product surface to be too rough or form an uneven hydrophobic layer, affecting the overall performance of the product.
[0065] In some optional examples, the mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride is 3 to 4 hours, for example, it can be 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional examples, the heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional examples, the mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours, for example, it can be 10.0 hours, 10.5 hours, 11.0 hours, 11.5 hours, 12.0 hours, 12.5 hours, 13.0 hours, 13.5 hours, 14.0 hours, 14.5 hours or 15.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the dialysis time is 5 to 8 days, for example, 5 days, 6 days, 7 days or 8 days, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In some optional embodiments, the freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] As a preferred technical solution of the present invention, in step (II), the intercalated montmorillonite is prepared by the following method:
[0073] The montmorillonite is dispersed in deionized water to obtain a montmorillonite suspension; under continuous stirring and water bath heating conditions, hexadecyltrimethylammonium bromide and caprolactam are sequentially added to the montmorillonite suspension to react, and after the reaction is completed, centrifugation is performed, and the precipitate obtained after the centrifugation is washed and dried to obtain the intercalated montmorillonite.
[0074] In some optional examples, the mass fraction of montmorillonite in the montmorillonite suspension is 2~5wt%, for example, it can be 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In some optional examples, the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:(0.3~0.5), for example, it can be 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.4, 1:0.42, 1:0.44, 1:0.46, 1:0.48 or 1:0.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] Montmorillonite is a clay mineral with a layered structure, and there are exchangeable cations between its layers, such as sodium ions and calcium ions. The interlayer spacing of unmodified montmorillonite is small. Through organic intercalation modification, the interlayer spacing of montmorillonite can be expanded, so that it can better load titanium dioxide and zinc oxide and play a synergistic role. Hexadecyltrimethylammonium bromide (CTAB) is a cationic surfactant, and its molecular structure contains a long-chain alkyl group and a positively charged quaternary ammonium cation. When intercalating montmorillonite, the action mechanism of CTAB is based on ion exchange and intermolecular forces. The cations between the montmorillonite layers will undergo ion exchange reactions with the quaternary ammonium cations of CTAB. Since the long-chain alkyl groups of CTAB molecules have large steric hindrance, after entering the interlayer of montmorillonite, they will open the montmorillonite layers, thereby increasing the interlayer spacing; at the same time, the van der Waals force between CTAB molecules and the interaction between the long-chain alkyl groups and the surface of the montmorillonite layers help CTAB to exist stably between the montmorillonite layers and maintain the enlarged interlayer spacing.
[0077] The dosage of CTAB will directly affect the intercalation modification effect on montmorillonite, and then affect the subsequent loading effect of titanium dioxide and zinc oxide. When the dosage of CTAB is within the numerical range specified in the present invention, effective intercalation modification of montmorillonite can be achieved, ensuring that the subsequently loaded titanium dioxide and zinc oxide are evenly distributed and have good photocatalytic performance, giving full play to the synergistic effect of nanocellulose, loaded modified montmorillonite and titanium dioxide and zinc oxide composite system, improving the photocatalytic barrier and antibacterial properties of the composite film, and meeting the actual needs of fruit and vegetable preservation.
[0078] When the amount of CTAB used is lower than the lower limit of the range defined in the present invention, the number of CTAB molecules participating in the ion exchange reaction is insufficient, and only part of the cations between the montmorillonite layers are replaced by the quaternary ammonium cations of CTAB, resulting in insufficient expansion of the interlayer spacing. First, it will affect the subsequent hydrophobic modification effect of the silane coupling agent on the loaded modified montmorillonite. Due to the small interlayer spacing, it is difficult for the silane coupling agent to fully enter the montmorillonite layers for reaction, and the surface properties of the montmorillonite cannot be effectively improved, which reduces its compatibility with the polymer matrix, resulting in the overall mechanical properties of the composite film, such as tensile strength and flexibility, cannot be effectively improved. Secondly, in the process of loading titanium dioxide and zinc oxide, the smaller interlayer spacing prevents the titanium precursor solution and the zinc precursor solution from entering the montmorillonite interlayer, resulting in the titanium precursor solution and the zinc precursor solution being unable to fully contact and react with the montmorillonite, making the amount of titanium dioxide and zinc oxide loaded in the montmorillonite interlayer small and unevenly distributed, which greatly affects the photocatalytic activity of the loaded modified montmorillonite, resulting in the inability of the loaded modified montmorillonite to produce sufficient hydroxyl radicals and superoxide anion radicals under photocatalysis, thereby weakening the inhibitory effect of the composite film on harmful microorganisms. Thirdly, the interlayer spacing of montmorillonite cannot be fully expanded, making it difficult to form a good barrier layered structure. Small molecules such as gas and water vapor are easily transmitted through the channels between the montmorillonite sheets and the pores in the composite film, which reduces the barrier performance of the composite film and is not conducive to the control of oxygen, carbon dioxide and water when preserving fruits and vegetables.
[0079] When the amount of CTAB exceeds the upper limit of the range defined in the present invention, first, the interlayer distance of montmorillonite will be excessively expanded, and too many CTAB molecules will gather between the montmorillonite layers, which will cause the interlayer structure to become unstable. In the subsequent processing process, such as centrifugation, washing and other steps, it is easy to cause the inserted CTAB molecules to partially detach from the montmorillonite interlayer, causing the retraction of the montmorillonite interlayer distance. Moreover, excessive CTAB will remain on the montmorillonite surface, affecting the reaction of the silane coupling agent with montmorillonite, and will also reduce the compatibility of montmorillonite with the polymer matrix. Secondly, when loading titanium dioxide and zinc oxide, the excessively expanded and unstable interlayer distance will make the distribution of titanium precursor solution and zinc precursor solution between the montmorillonite layers difficult to control, thereby causing the titanium dioxide and zinc oxide loaded to aggregate between the montmorillonite layers, and the aggregated titanium dioxide and zinc oxide particles reduce the contact area with light, reduce the generation efficiency of photogenerated carriers, and are also not conducive to the performance of photocatalytic performance. Thirdly, excessive intercalation makes the interlayer structure of montmorillonite unstable. In the subsequent melt extrusion process, the montmorillonite flakes are prone to slippage and dislocation, which destroys the uniformity and continuity of the composite system, thereby reducing the mechanical properties of the composite film.
[0080] In some optional examples, the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is (2-3):1, for example, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] Caprolactam is a cyclic amide compound. Combining it with CTAB for intercalation modification of montmorillonite can play a synergistic role. On the one hand, when CTAB is used alone for intercalation modification, the interlayer spacing of montmorillonite can be initially expanded, but the stability of the structure is poor. The nitrogen atoms and oxygen atoms in the caprolactam molecule have a certain electronegativity, which can form weak chemical bonds or strong intermolecular forces, such as hydrogen bonds and electrostatic attraction, with the cations on the surface of montmorillonite and some atoms in the CTAB molecule. This interaction enables caprolactam to be tightly attached to the surface of montmorillonite and the intercalation structure formed by CTAB and interweave with CTAB, stabilizing the interlayer spacing of montmorillonite supported by CTAB. In subsequent centrifugation, washing and other treatments, this synergistic structure effectively resists external interference and prevents CTAB from detaching and the interlayer spacing from shrinking. On the other hand, the cyclic structure of caprolactam can undergo intermolecular entanglement and π-π stacking with the long-chain alkyl groups of CTAB. This interaction acts like a "molecular bridge" that closely connects the two, allowing caprolactam to more effectively participate in the stabilization process of the intercalation structure, further stabilizing the intercalation structure of the intercalated montmorillonite. When caprolactam enters the interlayer of montmorillonite, the presence of its cyclic structure changes the chemical environment and physical properties of the interlayer, increases the flexibility and spatial complexity of the interlayer, and makes the lamellar structure of montmorillonite more stable.
[0082] CTAB and caprolactam synergistically enhance the performance in the intercalation modification of montmorillonite through ion exchange, intermolecular interaction and structural stabilization. CTAB is responsible for opening the interlayer spacing of montmorillonite, and caprolactam is responsible for consolidating and optimizing the structure of the opened sheets. The ratio of the two accurately regulates key factors such as the stability of the montmorillonite intercalation structure, the size of the interlayer spacing and the interlayer chemical environment, which not only affects the intercalation effect of montmorillonite, but is also closely related to the subsequent loading effect of titanium dioxide and zinc oxide. For this reason, the present invention specifically limits the mass ratio of hexadecyltrimethylammonium bromide to caprolactam to (2~3):1.
[0083] When the amount of CTAB exceeds the upper limit of the range defined in the present invention, the excess CTAB will form a thicker organic film on the surface of the montmorillonite, which not only prevents caprolactam from fully entering the montmorillonite interlayer to synergize with montmorillonite and CTAB, but also affects the subsequent loading effect of titanium dioxide and zinc oxide. It is difficult for caprolactam to fully exert its role in stabilizing the interlayer structure and improving the interlayer performance under such an environment, resulting in the unsatisfactory performance of the interlayered montmorillonite obtained. In addition, too much CTAB makes the interlayer environment of the montmorillonite disordered. When loading titanium dioxide and zinc oxide, after the titanium precursor solution and the zinc precursor solution enter the interlayer, due to the instability of the interlayer CTAB and the obstruction of the excessive organic film, it is difficult to evenly disperse in the montmorillonite interlayer, which will cause titanium dioxide and zinc oxide to locally over-aggregate in the montmorillonite interlayer to form agglomerated particles. The specific surface area of the agglomerated particles is greatly reduced. During the photocatalytic reaction, it is difficult for the photogenerated carriers to be effectively separated and migrated, which hinders the carrier transmission and reduces the photocatalytic activity. At the same time, after the unstable intercalation structure is loaded with titanium dioxide and zinc oxide, during subsequent use, affected by environmental factors such as temperature and humidity, CTAB may further detach from the interlayer, weakening the binding force between montmorillonite and the loaded titanium dioxide and zinc oxide. Titanium dioxide and zinc oxide are easily fallen off from the montmorillonite layer, resulting in the gradual loss of photocatalytic performance and the inability to continue to play a stable role.
[0084] When the amount of caprolactam exceeds the upper limit of the range defined in the present invention, due to the insufficient amount of CTAB, the montmorillonite interlayer cation exchange is insufficient, and the interlayer distance is limited. Although caprolactam can interact with the montmorillonite surface cations and CTAB, it is not possible to fully enter the interlayer of montmorillonite with the space opened by CTAB and stably exist. At this time, the intercalation structure of montmorillonite is difficult to effectively construct, and the sheets still maintain a relatively tight stacking state. In addition, excessive caprolactam will also cause it to form a disordered stacking structure on the montmorillonite surface, affecting the overall intercalation effect, so that montmorillonite cannot give full play to its barrier properties in subsequent applications. In addition, since the interlayer of montmorillonite cannot be effectively opened, the amount of titanium dioxide and zinc oxide loaded is small and scattered, and an effective photocatalytic active site network cannot be formed. The generated hydroxyl radicals, superoxide anion radicals and other active oxygen species are less, and it is difficult to effectively kill bacteria, resulting in a decrease in the photocatalytic performance and antibacterial properties of the composite film.
[0085] In some optional embodiments, the water bath heating temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some optional examples, after adding hexadecyltrimethylammonium bromide to the montmorillonite suspension, mixing and stirring are continued under heating conditions in a water bath for 10 to 20 minutes, and then caprolactam is added, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0087] In some optional examples, after adding caprolactam, mixing and stirring are continued under heating conditions in a water bath for 3 to 4 hours, for example, 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0088] In some optional examples, the centrifugal rotation speed is 7000~8000rpm, for example, it can be 7000rpm, 7100rpm, 7200rpm, 7300rpm, 7400rpm, 7500rpm, 7600rpm, 7700rpm, 7800rpm, 7900rpm or 8000rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0089] In some optional examples, the centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] As a preferred technical solution of the present invention, in step (II), the composite modified montmorillonite is prepared by the following method:
[0091] The silane coupling agent and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, the intercalated montmorillonite is added to the coupling agent solution, mixed and stirred and heated to react, and after the reaction is completed, filtered, washed and dried to obtain the composite modified montmorillonite.
[0092] In some optional examples, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is (8~9):1, for example, it can be 8.0:1, 8.1:1, 8.2:1, 8.3:1, 8.8:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1 or 9.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In some optional examples, the mass fraction of the silane coupling agent in the coupling agent solution is 1-5wt%, for example, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] In some optional examples, the mass ratio of the silane coupling agent in the coupling agent solution to the intercalated montmorillonite is (0.02~0.05):1, for example, it can be 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1 or 0.05:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] When the intercalated montmorillonite is hydrophobically modified, the silanol groups in the silane coupling agent molecules first undergo a condensation reaction with the hydroxyl groups on the surface of the montmorillonite to form a stable Si-O-Si chemical bond, thereby firmly grafting the silane coupling agent to the surface of the montmorillonite. At the same time, the organic functional groups at the other end of the silane coupling agent molecules extend outward, changing the chemical properties and physical structure of the montmorillonite surface, causing it to change from hydrophilic to hydrophobic.
[0096] The present invention particularly limits the mass ratio of the silane coupling agent to the loaded modified montmorillonite in the coupling agent solution to (0.02-0.05):1. When the amount of the silane coupling agent is lower than the lower limit of the range defined by the present invention, only a small amount of silane coupling agent molecules react with the montmorillonite surface, and most of the hydroxyl groups on the montmorillonite surface are still not covered, and its hydrophilicity is not effectively changed, which not only affects the dispersibility of the loaded modified montmorillonite in the polymer matrix, but also causes the loaded modified montmorillonite to absorb moisture in a humid environment, resulting in changes in its structure and performance, thereby affecting the performance of the composite film. In addition, when the dosage of silane coupling agent is too low, the surface hydrophobicity of montmorillonite is poor. In the process of loading titanium dioxide and zinc oxide, polar solvents (such as water and ethanol) in the titanium precursor solution and the zinc precursor solution are easy to aggregate on the surface of montmorillonite, making it difficult for the precursor solution to be evenly dispersed on the surface and interlayer of montmorillonite, resulting in uneven distribution of the loaded titanium dioxide and zinc oxide, and agglomeration. It is difficult for photogenerated carriers to be effectively transmitted in the agglomerates, resulting in a reduction in the number of active sites for the photocatalytic reaction, which ultimately affects the photocatalytic and antibacterial properties of the composite film.
[0097] When the amount of silane coupling agent exceeds the upper limit of the range defined in the present invention, the excessive silane coupling agent is excessively accumulated on the surface of montmorillonite. Although the hydrophobicity of montmorillonite can be further enhanced, the excessive silane coupling agent molecules will agglomerate to form some larger aggregates. These aggregates will not only reduce the effective binding sites between the silane coupling agent and the surface of montmorillonite, but also form an uneven structure on the surface of montmorillonite, hindering the effective contact and reaction between the titanium precursor solution and the zinc precursor solution and the surface of montmorillonite, thereby causing the binding force between the loaded titanium dioxide and zinc oxide and montmorillonite to decrease, and in the subsequent use process, it is easy to fall off. In addition, the agglomerated silane coupling agent will also wrap part of the precursor, affecting the hydrolysis and polycondensation reaction of the precursor, so that the crystal structure and morphology of the loaded titanium dioxide and zinc oxide are affected, further reducing the photocatalytic performance and antibacterial performance of the composite film.
[0098] In some optional examples, the reaction temperature of the intercalated montmorillonite and the coupling agent solution is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0099] In some optional examples, the reaction time of the intercalated montmorillonite and the coupling agent solution is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0100] As a preferred technical solution of the present invention, in step (III), the volume ratio of tetrabutyl titanate, triethanolamine and anhydrous ethanol is 1:(5-6):(50-60), for example, it can be 1:5:50, 1:5.1:51, 1:5.2:52, 1:5.3:53, 1:5.4:54, 1:5.5:55, 1:5.6:56, 1:5.7:57, 1:5.8:58, 1:5.9:59 or 1:6:60, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0101] In some optional examples, the concentration of zinc acetate in the zinc precursor solution is 6-7 g / L, for example, 6.0 g / L, 6.1 g / L, 6.2 g / L, 6.3 g / L, 6.4 g / L, 6.5 g / L, 6.6 g / L, 6.7 g / L, 6.8 g / L, 6.9 g / L or 7.0 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0102] In some optional examples, the mass ratio of urea, sodium citrate and deionized water in the zinc precursor solution is 1:(0.2~0.3):(10~15), for example, it can be 1:0.2:10, 1:0.21:10.5, 1:0.22:11, 1:0.23:11.5, 1:0.24:12, 1:0.25:12.5, 1:0.26:13, 1:0.27:13.5, 1:0.28:14, 1:0.29:14.5 or 1:0.3:15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In some optional examples, the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 3~5wt%, for example, it can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0104] In some optional examples, the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water in the montmorillonite dispersion is (3~5):(2~3):1, for example, it can be 3:2:1, 3.2:2.1:1, 3.4:2.2:1, 3.6:2.3:1, 3.8:2.4:1, 4:2.5:1, 4.2:2.6:1, 4.4:2.7:1, 4.6:2.8:1, 4.8:2.9:1 or 5:3:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0105] In some optional examples, the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is (2~2.5) mL:1g, for example, it can be 2.0 mL:1g, 2.05 mL:1g, 2.1 mL:1g, 2.15 mL:1g, 2.2 mL:1g, 2.25 mL:1g, 2.3 mL:1g, 2.35 mL:1g, 2.4 mL:1g, 2.45 mL:1g or 2.5 mL:1g, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0106] Tetrabutyl titanate (TBOT) is a precursor of titanium dioxide. Its ratio with the composite modified montmorillonite has a significant effect on the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the final loaded modified montmorillonite. TBOT is converted into titanium dioxide through hydrolysis and polycondensation under a specific reaction system. TBOT is mixed with triethanolamine and anhydrous ethanol to prepare a titanium precursor solution, which is then dropped into the montmorillonite dispersion. The hydrolysis reaction occurs first, and the reaction formula is:
[0107]
[0108] The Ti(OH )4 Unstable, then a polycondensation reaction occurs, gradually forming a precursor polymer of titanium dioxide, and finally generating anatase or rutile titanium dioxide. The polycondensation reaction is simplified as:
[0109]
[0110] The present invention specifically limits the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion to (2~2.5)mL:1g. When the amount of tetrabutyl titanate used is lower than the lower limit of the range defined by the present invention, the amount of titanium dioxide generated by hydrolysis and polycondensation is too small. After being loaded on the composite modified montmorillonite, the photocatalytic active sites are scarce. Under light, the number of photogenerated carriers (electron-hole pairs) generated is limited, and it is difficult to meet the photocatalytic reaction requirements. When degrading harmful gases such as ethylene generated during the preservation of fruits and vegetables, due to active oxygen species (such as hydroxyl radicals·OH, superoxide anion radicals·O2 - ) is generated in small amounts, the photocatalytic efficiency is reduced, and ethylene cannot be quickly degraded, which in turn cannot effectively delay the ripening and decay of fruits and vegetables. In addition, due to the small amount of titanium dioxide loaded, it is impossible to effectively fill the gaps between montmorillonite layers and cover the surface, and it is difficult to form a dense barrier structure. During the preservation of fruits and vegetables, small molecules such as oxygen and water vapor can easily penetrate the gaps between montmorillonite layers, resulting in a decrease in the barrier performance of the composite film, accelerating the oxidation of fruits and vegetables and the loss of water, and shortening the shelf life of fruits and vegetables.
[0111] When the amount of tetrabutyl titanate exceeds the upper limit of the range defined in the present invention, the excess tetrabutyl titanate will cause the titanium dioxide particles generated by hydrolysis and polycondensation to aggregate excessively on the surface and interlayer of the composite modified montmorillonite, and the specific surface area of the agglomerated titanium dioxide particles will be reduced, which will not only extend the transmission distance of the photogenerated carriers, but also hinder the absorption and scattering of light, reduce the action area of light and titanium dioxide, and greatly reduce the photocatalytic performance of the composite film; at the same time, the agglomerated titanium dioxide will also become a stress concentration point, affecting the mechanical properties of the composite film, and may also affect the transparency of the composite film. In addition, too much titanium dioxide aggregates on montmorillonite, which will destroy the original layered structure of montmorillonite. In the subsequent treatment process, it is very easy to cause the layered structure of montmorillonite to collapse or deform, affecting its dispersion and orientation in the composite film, which will not only affect the decline in the mechanical properties of the composite film, but also form defective channels inside the composite film, increase the gas and water vapor permeability, and ultimately lead to a decline in the barrier performance of the composite film.
[0112] Most importantly, the amount of tetrabutyl titanate also affects the crystal form of the generated titanium dioxide, and the crystal form of titanium dioxide further directly determines the photocatalytic performance of the composite film. Common crystal forms of titanium dioxide are anatase and rutile. In the process of hydrolysis and polycondensation of tetrabutyl titanate to generate titanium dioxide, the concentration of reactants will affect the crystal structure of the final generated titanium dioxide. When the amount of tetrabutyl titanate is too low, the titanium source participating in the reaction in the system is limited. During the hydrolysis and polycondensation process, the reaction rate is relatively slow, and the concentration of the generated titanium dioxide precursor is low, which makes the arrangement and aggregation of atoms in the crystal growth process more inclined to form anatase crystal structure with a relatively loose crystal structure. Moreover, due to the small amount of tetrabutyl titanate, the energy and material basis provided by the reaction system are limited, and it is difficult to promote the further transformation of anatase titanium dioxide to a denser rutile type. Therefore, a lower reactant concentration is conducive to the generation of anatase titanium dioxide.
[0113] When the dosage of tetrabutyl titanate is too high, the excessive amount of tetrabutyl titanate makes the titanium source in the system sufficient, the hydrolysis and condensation reaction rate is accelerated, and the concentration of the generated titanium dioxide precursor increases rapidly. As the reaction proceeds, the higher reactant concentration and the local high temperature environment generated during the reaction provide more sufficient energy and material conditions for the growth of titanium dioxide crystals, which makes it easier for the crystals to arrange in a rutile-type close stacking manner during the growth process, thereby being more inclined to generate rutile titanium dioxide; at the same time, the large amount of by-products (such as butanol) generated by the hydrolysis of excessive tetrabutyl titanate will also change the environment of the reaction system, further promoting the formation of rutile titanium dioxide. Therefore, a higher reactant concentration is more inclined to form rutile titanium dioxide.
[0114] The band gap of anatase titanium dioxide is about 3.2eV, and the band gap of rutile titanium dioxide is about 3.0eV. During the photocatalytic process, when titanium dioxide is exposed to light with energy greater than its band gap, it will generate photogenerated carriers (electron-hole pairs). Since the band gap of anatase titanium dioxide is larger, the photogenerated carriers it generates have higher energy and theoretically have stronger redox ability. However, there are many defects and vacancies in the crystal structure of anatase titanium dioxide, which will become the recombination centers of photogenerated carriers, resulting in an increase in the recombination probability of photogenerated carriers. In contrast, the crystal structure of rutile titanium dioxide is relatively dense, and the recombination probability of photogenerated carriers is relatively low, but due to its small band gap, the energy of the photogenerated carriers generated is relatively low. Therefore, in the composite film, if titanium dioxide is mainly anatase, although its photogenerated carriers have higher energy, the higher recombination probability will reduce its photocatalytic efficiency. When degrading harmful gases produced during the preservation of fruits and vegetables, although it has a strong oxidizing ability, it cannot continuously provide sufficient hydroxyl radicals OH and superoxide anion radicals O2 due to the rapid recombination of carriers.- , resulting in unsatisfactory photocatalytic degradation effect. When titanium dioxide is mainly rutile, although the probability of photogenerated carrier recombination is low, the low energy will make it insufficiently active in some photocatalytic reactions, which also affects the photocatalytic efficiency of the composite film.
[0115] Therefore, in order to obtain a composite film with ideal photocatalytic performance, it is necessary to form a certain synergistic effect between anatase and rutile titanium dioxide. When the two coexist in a suitable ratio, the high-energy photogenerated carriers generated by anatase titanium dioxide can be quickly transferred to rutile titanium dioxide, and the lower recombination probability of rutile is utilized to achieve effective separation and utilization of photogenerated carriers, thereby improving the photocatalytic performance of the composite film. The amount of tetrabutyl titanate will indirectly affect the performance of this synergistic effect by affecting the crystal form composition of titanium dioxide. If the amount of tetrabutyl titanate is improper, resulting in excessive generation of a certain crystal form, this synergistic relationship will be destroyed, and the photocatalytic performance of the composite film will be reduced. Based on this, the present invention specifically limits the ratio of tetrabutyl titanate to composite modified montmorillonite to (2~2.5) mL: 1g, so as to obtain titanium dioxide with a suitable crystal form ratio to meet the requirements for the photocatalytic performance of the composite film.
[0116] In some optional examples, the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is (2~2.5):1, for example, it can be 2.0:1, 2.05:1, 2.1:1, 2.15:1, 2.2:1, 2.25:1, 2.3:1, 2.35:1, 2.4:1, 2.45:1 or 2.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0117] Zinc acetate is a precursor of zinc oxide, and its mass ratio to composite modified montmorillonite has a significant effect on the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the final loaded modified montmorillonite. Controlling the mass ratio of zinc acetate to composite modified montmorillonite within a reasonable range of (2~2.5):1 can ensure that an appropriate amount of zinc oxide is loaded evenly on the composite modified montmorillonite, give full play to its synergistic effect with titanium dioxide, improve the photocatalytic performance, and achieve efficient preservation of fruits and vegetables.
[0118] Zinc acetate will undergo hydrolysis in aqueous solution. The hydrolysis process is relatively complicated. First, zinc acetate is ionized under the action of water:
[0119]
[0120] Ionization of Zn 2+ It quickly coordinates with a large number of surrounding water molecules to form hydrated zinc ions [Zn(H2O) n] 2+ As the reaction proceeds, urea in the system is hydrolyzed to produce alkaline substances NH3·H2O, which increases the alkalinity of the solution. n ] 2+ It will gradually lose protons and undergo hydrolysis, and after a series of hydrolysis and condensation reactions, zinc oxide will eventually be generated.
[0121] The present invention specifically limits the mass ratio of zinc acetate to the composite modified montmorillonite to (2-2.5):1. When the amount of zinc acetate used is lower than the lower limit of the range defined in the present invention, on the one hand, due to the small amount of zinc oxide generated, after being loaded on the composite modified montmorillonite, the photocatalytic active sites are insufficient. In the photocatalytic process, the number of photogenerated carriers synergistically generated by zinc oxide and titanium dioxide is limited. Since the synergistic effect of the two depends on sufficient active sites to realize the transfer and utilization of photogenerated carriers, insufficient sites lead to the inability to effectively generate sufficient hydroxyl radicals ·OH and superoxide anion radicals ·O2 with strong oxidizing properties. - When active oxygen species such as zinc oxide and other active oxygen species are used to degrade harmful gases such as ethylene produced during the preservation of fruits and vegetables, their photocatalytic efficiency is low and they cannot effectively delay the ripening and decay of fruits and vegetables. On the other hand, an appropriate amount of zinc oxide loading can enhance the interaction between montmorillonite layers and improve structural stability, but too little zinc oxide cannot effectively fill the gaps between montmorillonite layers. There is a lack of sufficient zinc oxide between the montmorillonite layers for support and connection, which makes it difficult for the montmorillonite layers to form a dense barrier structure. Under the influence of external environmental factors (such as temperature and humidity changes), the montmorillonite layers are prone to displacement or deformation, thereby forming more gas and water vapor transmission channels. During the preservation of fruits and vegetables, small molecules such as oxygen and water vapor can easily enter through the gaps between the montmorillonite layers, accelerating the oxidation and water loss of fruits and vegetables, and shortening the shelf life of fruits and vegetables. On the other hand, due to the small amount of zinc oxide generated, it is difficult to form an effective synergistic network with titanium dioxide. During the photocatalytic process, the transfer and recombination process of photogenerated carriers between the two are hindered. The photogenerated carriers generated by titanium dioxide cannot be fully transferred to zinc oxide for effective utilization, which reduces the separation efficiency and utilization efficiency of photogenerated carriers, resulting in insufficient generation of reactive oxygen species, greatly weakening the ability of photocatalytic degradation of harmful gases (such as ethylene) in fruit and vegetable preservation, and cannot effectively delay the ripening and decay of fruits and vegetables.
[0122] When the amount of zinc acetate exceeds the upper limit of the range defined in the present invention, on the one hand, excessive zinc acetate will cause the generated zinc oxide to aggregate excessively on the surface and interlayer of the composite modified montmorillonite, and the agglomerated zinc oxide ions will cause its specific surface area to decrease, so that the transmission distance of the photogenerated carriers inside the zinc oxide is significantly increased, the transmission efficiency of the photogenerated carriers is reduced, and the recombination probability rises sharply during the transmission process. The photogenerated carriers inside the agglomerated zinc oxide particles may not have migrated to the particle surface to participate in the reaction, but have already recombinated with holes, greatly reducing the effective utilization rate of the photogenerated carriers. On the other hand, excessive zinc oxide will break the optimal ratio relationship between zinc oxide and titanium dioxide, resulting in changes in the energy band matching and interface interaction between the two. The agglomerated zinc oxide will not only reduce its effective contact area with titanium dioxide, so that the transfer efficiency of the photogenerated carriers at the interface is reduced, but also cover part of the active sites of titanium dioxide, hindering the contact of titanium dioxide with light and the generation and transmission of photogenerated carriers. At the same time, too many zinc oxide particles will also introduce some impurity energy levels, which become the recombination centers of photogenerated carriers, making the transmission of photogenerated carriers in the composite system disordered, seriously interfering with the photocatalytic reaction process, hindering the electron transmission and photocatalytic reaction process of the entire composite system, and causing the photocatalytic performance of the composite film to drop significantly. On the other hand, too many zinc oxide particles gather on the surface and interlayer of montmorillonite. These aggregated zinc oxide particles will squeeze and destroy the original layered structure of montmorillonite, and will destroy the original layered structure of montmorillonite. In the subsequent processing process, such as centrifugation, washing, drying and calcination, the structure of montmorillonite will deform or collapse, disrupting the orderly arrangement between montmorillonite sheets, forming some irregular large pores, which become channels for rapid transmission of gas and water vapor, and finally appear defective channels inside the composite film. These defective channels will increase the permeability of gas and water vapor, reduce the barrier performance of the composite film, and affect the preservation effect of fruits and vegetables.
[0123] In some optional examples, the dripping process of the titanium precursor solution and the zinc precursor solution is specifically as follows:
[0124] Under stirring and heating conditions, first, the titanium precursor solution is dripped into the montmorillonite dispersion, and after the titanium precursor solution is completely dripped, an intermediate solution is obtained, and the intermediate solution is continuously mixed and stirred under heating conditions for 2 to 3 hours, for example, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours; then, the zinc precursor solution is continuously dripped into the intermediate solution under stirring and heating conditions, and after the zinc precursor solution is completely dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred under heating conditions for 10 to 12 hours, for example, 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, to obtain the composite sol.
[0125] In some optional examples, the heating temperature during the process of adding the titanium precursor solution is 180~200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0126] The present invention specifically limits the heating temperature in the process of dripping the titanium precursor solution to 180-200°C, aiming to obtain titanium dioxide in which anatase and rutile coexist. When the reaction temperature is within the range of 180-200°C, on the one hand, the temperature range provides suitable conditions for the hydrolysis and polycondensation reaction of the titanium precursor, and the higher temperature accelerates the hydrolysis rate of tetrabutyl titanate, so that the titanium ions in the system are rapidly hydroxylated, and a large amount of titanium hydroxy compounds are generated, creating abundant sites for crystal nucleation. In this temperature range, the nucleation process of anatase and rutile titanium dioxide is promoted and occurs at the same time, but there is a difference in the nucleation rate of the two. The crystal structure of rutile titanium dioxide is more compact, and its nucleation requires atoms to have higher energy to overcome a larger potential barrier. The temperature range of 180-200°C gives atoms enough energy, so that they have the opportunity to migrate to the lattice position of the rutile type for nucleation. At the same time, the relatively low energy allows the nucleation of the anatase type to continue to occur, thereby realizing the common nucleation of the two crystal forms.
[0127] On the other hand, the temperature range of 180~200℃ affects the diffusion rate of atoms. The crystal structure of anatase titanium dioxide is relatively loose, and atomic diffusion is relatively easy. In this temperature range, although atoms have a certain diffusion ability, they do not diffuse too fast, so that anatase crystals can gradually grow while maintaining their own structural stability. For rutile titanium dioxide, this temperature range provides just enough energy for its atomic diffusion. Atoms can overcome the diffusion barrier and migrate to the lattice position of the rutile type, promoting the growth of rutile crystals. Since the growth rates of the two crystal forms reach a balance in this temperature range, anatase and rutile titanium dioxide can grow together in the same system.
[0128] On the other hand, according to the principles of thermodynamics, the free energy of the system changes with temperature. In the temperature range of 180-200°C, the difference in free energy between anatase and rutile titanium dioxide is in a special range, which makes both crystal forms have certain stability. Although rutile titanium dioxide is more thermodynamically stable at higher temperatures, the temperature range of 180-200°C does not make the system completely inclined to the transformation of rutile, and anatase can still exist stably, thus achieving the coexistence of the two crystal forms.
[0129] When the reaction temperature is lower than 180°C, the hydrolysis and polycondensation reaction rates of the titanium precursor are significantly reduced, and the number of titanium hydroxy compounds produced by hydrolysis is reduced, resulting in insufficient crystal nucleation sites and a slow nucleation process. For the nucleation of rutile titanium dioxide, the lower temperature makes the atomic energy insufficient, making it difficult to overcome the higher potential barrier required for the formation of the rutile lattice. The nucleation of rutile is greatly inhibited, or even fails to nucleate. During the crystal growth stage, the atomic diffusion rate also drops significantly, and the anatase titanium dioxide crystals grow slowly and incompletely, with more defects in the crystal structure. In addition, low temperature makes the system more inclined to maintain the stability of the anatase type, because the transformation of the anatase type to the rutile type requires higher energy, and low temperature cannot provide this condition. The final product is mainly anatase titanium dioxide, and even some amorphous titanium dioxide exists, which seriously affects the photocatalytic properties of titanium dioxide and the antibacterial properties of the composite film.
[0130] When the reaction temperature is higher than 200°C, the hydrolysis and polycondensation reaction rates of the titanium precursor are extremely fast, a large number of crystal nucleation sites are formed instantly, and the nucleation rate of rutile titanium dioxide far exceeds that of anatase. Because the high temperature gives atoms extremely high energy, the atomic diffusion rate increases sharply, and the rutile crystals grow rapidly and soon become dominant. In addition, high temperature greatly reduces the free energy of rutile titanium dioxide, which is far lower than that of anatase. The transformation from anatase to rutile is rapid and thorough. The final product is almost entirely rutile titanium dioxide, and the coexistence of the two crystal forms cannot be achieved, which will also affect the photocatalytic and antibacterial properties of the composite film in the preservation of fruits and vegetables.
[0131] In some optional examples, the stirring speed during the process of adding the titanium precursor solution is 700~800r / min, for example, it can be 700r / min, 710r / min, 720r / min, 730r / min, 740r / min, 750r / min, 760r / min, 770r / min, 780r / min, 790r / min or 800r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0132] In some optional examples, the dripping rate of the titanium precursor solution is 4~6mL / min, for example, it can be 4.0mL / min, 4.2mL / min, 4.4mL / min, 4.6mL / min, 4.8mL / min, 5.0mL / min, 5.2mL / min, 5.4mL / min, 5.6mL / min, 5.8mL / min or 6.0mL / min, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0133] In some optional examples, the heating temperature during the process of adding the zinc precursor solution is 160-180°C, for example, it can be 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0134] In some optional examples, the stirring speed during the process of adding the zinc precursor solution is 700~800r / min, for example, it can be 700r / min, 710r / min, 720r / min, 730r / min, 740r / min, 750r / min, 760r / min, 770r / min, 780r / min, 790r / min or 800r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0135] In some optional examples, the dripping rate of the zinc precursor solution is 4~6mL / min, for example, it can be 4.0mL / min, 4.2mL / min, 4.4mL / min, 4.6mL / min, 4.8mL / min, 5.0mL / min, 5.2mL / min, 5.4mL / min, 5.6mL / min, 5.8mL / min or 6.0mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0136] In some optional examples, the aging time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0137] In some optional instances, the drying temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C or 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0138] In some optional examples, the drying time is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0139] In some optional embodiments, the calcination temperature is 500-550°C, for example, it can be 500°C, 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, 545°C or 550°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0140] In some optional examples, the calcination time is 6 to 8 hours, for example, it can be 6.0h, 6.2h, 6.4h, 6.6h, 6.8h, 7.0h, 7.2h, 7.4h, 7.6h, 7.8h or 8.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0141] As a preferred technical solution of the present invention, in step (IV), the weight proportions of the components in the mixed material are as follows:
[0142] Polylactic acid 80-85 parts;
[0143] 8-10 parts of quaternary ammonium sulfonated nanocellulose;
[0144] Loading modified montmorillonite 5-8 parts;
[0145] 1~2 parts of plasticizer;
[0146] Lubricant 0.5~1.5 parts;
[0147] Antioxidant 0.1~0.5 parts.
[0148] Among them, the weight parts of polylactic acid can be 80 parts, 80.5 parts, 81 parts, 81.5 parts, 82 parts, 82.5 parts, 83 parts, 83.5 parts, 84 parts, 84.5 parts or 85 parts; the weight parts of quaternary ammonium sulfonated nanocellulose can be 8.0 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts, 9.0 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts or 10.0 parts; the weight parts of loaded modified montmorillonite can be 5.0 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6.0 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7.0 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts or 8.0 parts by weight; the weight portion of the plasticizer can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0 parts; the weight portion of the lubricant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5 parts; the weight portion of the antioxidant can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5 parts, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0149] In some optional examples, the plasticizer includes any one of triacetin, tributyl sodium citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl sodium citrate tributyl ester, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof.
[0150] In some optional examples, the lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof.
[0151] In some optional examples, the antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.
[0152] As a preferred technical solution of the present invention, in step (V), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction.
[0153] In some optional instances, the temperature of the first zone is 150-160°C, for example, it may be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0154] In some optional instances, the temperature of the second zone is 160-170°C, for example, it may be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0155] In some optional instances, the temperature of the third zone is 170-180°C, for example, it may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0156] In some optional instances, the temperature of the fourth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0157] In some optional examples, the temperature of the fifth zone is 185-190°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0158] In some optional examples, the temperature of the sixth zone is 190-195°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0159] In some optional examples, the temperature of the seventh zone is 200-205°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0160] In some optional examples, the temperature of the eighth zone is 195-200°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0161] In some optional instances, the head temperature of the screw extruder is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0162] In some optional examples, the screw speed of the screw extruder is 200~300rpm, for example, it can be 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0163] In some optional examples, the film blowing process is carried out in a film blowing machine, and the interior of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction.
[0164] In some optional instances, the temperature of the ninth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0165] In some optional instances, the temperature of the tenth zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0166] In some optional instances, the temperature of the eleventh zone is 185-195°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0167] In some optional instances, the temperature of the twelfth zone is 195-205°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0168] In some optional instances, the temperature of the thirteenth zone is 190-200°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C, 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0169] In some optional examples, the screw speed of the film blowing machine is 100~200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0170] In some optional examples, the traction speed of the film blowing machine is 5~10m / min, for example, it can be 5.0m / min, 5.5m / min, 6.0m / min, 6.5m / min, 7.0m / min, 7.5m / min, 8.0m / min, 8.5m / min, 9.0m / min, 9.5m / min or 10.0m / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0171] In some optional examples, the blowing ratio of the film blowing machine is 2 to 5, for example, 2, 3, 4 or 5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0172] In a second aspect, the present invention provides a photocatalytic barrier composite film for preserving fruits and vegetables, which is prepared by the preparation method described in the first aspect, and the photocatalytic barrier composite film comprises polylactic acid, quaternary ammonium sulfonated nanocellulose, loaded modified montmorillonite, a plasticizer, a lubricant and an antioxidant.
[0173] Compared with the prior art, the present invention has the following beneficial effects:
[0174] The photocatalytic barrier composite film prepared by the present invention has excellent photocatalytic performance, antibacterial performance, barrier performance and mechanical properties. In the preparation process, the present invention firstly treats the nanocellulose by sulfonation and quaternization modification, thereby improving its dispersibility and compatibility in the polymer matrix, and then enhancing the mechanical properties and barrier properties of the composite film. Subsequently, the montmorillonite is organically intercalated with hexadecyltrimethylammonium bromide and caprolactam to increase the interlayer spacing of the montmorillonite, and then the intercalated montmorillonite is hydrophobically modified by a silane coupling agent to obtain a composite modified montmorillonite. Finally, titanium dioxide and zinc oxide are loaded on the interlayer and surface of the composite modified montmorillonite by a sol-gel method, and the different energy band structures of titanium dioxide and zinc oxide are used to give the loaded modified montmorillonite excellent photocatalytic ability, so that the final composite film can use light of different wavelengths to produce more active oxygen species, efficiently decompose ripening gases such as ethylene, and inhibit the ripening and aging of fruits and vegetables.
[0175] The present invention combines the high specific surface area and high strength of quaternary ammonium sulfonated nanocellulose with the layered structure and photocatalytic performance of the loaded modified montmorillonite, thereby enhancing the mechanical properties of the composite film while greatly improving its barrier properties, and can form a tortuous gas permeation path in the polymer matrix, thereby delaying the respiration and water loss of fruits and vegetables; at the same time, the quaternary ammonium sulfonated nanocellulose itself is antibacterial, and the active oxygen species generated by the loaded modified montmorillonite through photocatalysis can destroy bacterial cell walls and cell membranes, and the synergistic effect of the two can significantly enhance the antibacterial properties of the composite film, reduce microbial contamination, and ensure the freshness of fruits and vegetables.
[0176] Compared with traditional chemical preservation products, the composite film prepared by the present invention utilizes physical barrier effect and photocatalysis to achieve the preservation effect, does not rely on chemical reagents, and can be used to wrap fruits and vegetables with the composite film. No harmful substances will remain on the surface or inside of the fruits and vegetables, and no harm will be caused to human health and the environment. It meets the requirements of green environmental protection and food safety, and can provide consumers with safer and healthier fruit and vegetable products. BRIEF DESCRIPTION OF THE DRAWINGS
[0177] Figure 1 A process flow chart of the preparation of the photocatalytic barrier composite film for preserving fruits and vegetables provided in Examples 1-5 of the present invention;
[0178] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention and quaternary ammonium sulfonated nanocellulose;
[0179] Figure 3 zeta potential diagrams of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention, and quaternary ammonium sulfonated nanocellulose;
[0180] Figure 4 XRD diagrams of montmorillonite and intercalated montmorillonite prepared in Example 1 of the present invention;
[0181] Figure 5 The infrared spectra of montmorillonite and the intercalated montmorillonite prepared in Example 1 of the present invention;
[0182] Figure 6 This is a scanning electron microscope image of the montmorillonite used in Example 1 of the present invention;
[0183] Figure 7 This is a scanning electron microscope image of the intercalated montmorillonite prepared in Example 1 of the present invention;
[0184] Figure 8 This is a transmission electron microscope image of the montmorillonite used in Example 1 of the present invention;
[0185] Fig. 9 This is a transmission electron microscope image of the intercalated montmorillonite prepared in Example 1 of the present invention;
[0186] Fig.10 The water contact angle diagrams of montmorillonite, intercalated montmorillonite prepared in Example 1 of the present invention, and composite modified montmorillonite;
[0187] Fig.11 XRD diagram of the loaded modified montmorillonite prepared in Example 1, Example 8 and Example 9 of the present invention;
[0188] Fig.12 This is a scanning electron microscope image of the composite modified montmorillonite prepared in Example 1 of the present invention;
[0189] Fig.13 This is a scanning electron microscope image of the loaded modified montmorillonite prepared in Example 1 of the present invention;
[0190] Fig.14 This is a transmission electron microscope image of the composite modified montmorillonite prepared in Example 1 of the present invention;
[0191] Fig.15This is a transmission electron microscope image of the loaded modified montmorillonite prepared in Example 1 of the present invention;
[0192] Fig.16 The actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in the green vegetable preservation experiment;
[0193] Fig.17 The following are actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in a mango preservation experiment. DETAILED DESCRIPTION
[0194] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0195] Example 1
[0196] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0197] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 5 wt% (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:50 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 300 W for 40 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 50 °C for 5 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4 wt%, and add the mixture to the nanocellulose suspension. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.14, the mixture was mixed and stirred at 60°C for 6 hours, and a reaction product was obtained after the reaction was completed. A 5wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 2, and then the reaction product was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 10000Da. After the dialysis was completed, the dialyzed product was placed at -60°C for freeze-drying for 12 hours to obtain sulfonated nanocellulose;
[0198] The sulfonated nanocellulose was added to triethylamine in a ratio of 1 g:30 mL, and then ultrasonically dispersed for 40 min at an ultrasonic power of 300 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.2, and mixed and stirred at 60° C. for 4 h, and then heating was stopped, and mixed and stirred at room temperature for 15 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 10000 Da, and after the dialysis, the dialyzed product was freeze-dried at -40° C. for 24 h to obtain quaternary ammonium sulfonated nanocellulose;
[0199] (2) dispersing montmorillonite in deionized water to obtain a montmorillonite suspension with a mass fraction of 2 wt%; adding hexadecyltrimethylammonium bromide to the montmorillonite suspension under continuous stirring and heating in a water bath at 70°C, wherein the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:0.3; mixing and stirring for 20 minutes in a water bath at 70°C; then adding caprolactam, wherein the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is 2:1; continuing to mix and stir for 4 hours in a water bath at 70°C; after the reaction is completed, centrifuging at a speed of 7000 rpm for 20 minutes; washing and drying the precipitate obtained after centrifugation to obtain intercalated montmorillonite;
[0200] The silane coupling agent KH550 and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8:1, and the mass fraction of the silane coupling agent KH550 in the coupling agent solution is 1wt%; the intercalated montmorillonite is added to the coupling agent solution, the mass ratio of the silane coupling agent KH550 to the intercalated montmorillonite in the coupling agent solution is 0.02:1, the mixture is mixed and stirred at 70°C for 5h to react, and after the reaction is completed, the mixture is filtered, washed and dried to obtain a composite modified montmorillonite;
[0201] (3) Tetrabutyl titanate, triethanolamine and anhydrous ethanol are mixed uniformly in a volume ratio of 1:5:50 to obtain a titanium precursor solution; zinc acetate, urea, sodium citrate and deionized water are mixed uniformly to obtain a zinc precursor solution, wherein the concentration of zinc acetate in the zinc precursor solution is 6 g / L, and the mass ratio of urea, sodium citrate and deionized water is 1:0.2:10; composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water are mixed uniformly to obtain a montmorillonite dispersion, wherein the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 3wt%, and the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water is 3:2:1;
[0202] Under the conditions of a stirring speed of 700 r / min and a heating temperature of 180°C, a titanium precursor solution was dripped into the montmorillonite dispersion at a dripping rate of 4 mL / min, and the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion was 2 mL:1 g; after all the titanium precursor solution was dripped, an intermediate solution was obtained, and the same stirring and heating conditions were maintained, and the intermediate solution was continued to be mixed and stirred for 3 hours; then, under the conditions of a stirring speed of 700 r / min and a heating temperature of 160°C, a titanium precursor solution was dripped at a dripping rate of 4 mL / min. A zinc precursor solution is dripped into the intermediate solution, wherein the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is 2:1, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 12 hours under heating conditions to obtain a composite sol; the composite sol is sequentially aged, centrifuged, washed, dried and calcined to obtain a loaded modified montmorillonite, wherein the aging time is 12 hours, the drying temperature is 60° C., the drying time is 12 hours, the calcination temperature is 500° C., and the calcination time is 8 hours;
[0203] (4) 80 parts of polylactic acid, 10 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 8 parts of loaded modified montmorillonite obtained in step (3), 1 part of ethylene glycol, 0.5 parts of calcium stearate and 0.5 parts of antioxidant 1010 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 150° C., the temperature of the second zone is 160° C., the temperature of the third zone is 170° C., the temperature of the fourth zone is 175° C., the temperature of the fifth zone is 185° C., the temperature of the sixth zone is 190° C., the temperature of the seventh zone is 200° C., the temperature of the eighth zone is 195° C., the head temperature is 180° C., and the screw speed is 200 rpm;
[0204] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 175°C, the temperature of the tenth zone is 180°C, the temperature of the eleventh zone is 185°C, the temperature of the twelfth zone is 195°C, and the temperature of the thirteenth zone is 190°C. The screw speed of the film blowing machine is 100rpm, the traction speed of the film blowing machine is 5m / min, and the blowing ratio of the film blowing machine is 2. After film blowing, the photocatalytic barrier composite film is obtained.
[0205] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in this example, and quaternary ammonium sulfonated nanocellulose are shown in Figure 1. In the infrared spectrum curve of nanocellulose, 3284 cm -1 The corresponding OH stretching vibration absorption peak is 1038 cm -1 The corresponding absorption peak is the stretching vibration of CO.
[0206] In the infrared spectrum of sulfonated nanocellulose, 1375 cm -1 and 896cm -1 The stretching vibration absorption peaks corresponding to O=S=O and COS of the sulfonic acid functional group respectively indicate that the sulfonic acid functional group is successfully connected to the molecular chain of nanocellulose.
[0207] In the infrared spectrum curve of quaternary ammonium sulfonated nanocellulose, the stretching vibration absorption peak of OH is from 3284 cm -1 Offset to 3359cm -1 This is because the electrostatic effect of the introduced quaternary ammonium functional groups changes the forces between hydrogen bonds in nanocellulose. In addition, 2905cm -1 and 2846cm -1 The asymmetric stretching vibration and symmetric stretching vibration absorption peaks of -CH2- in the molecular chain of octadecyltrimethylammonium chloride are 1433 cm -1 The corresponding peak is the stretching vibration absorption peak of the trimethyl functional group in the molecular chain of octadecyltrimethylammonium chloride, which indicates that octadecyltrimethylammonium chloride is successfully connected to the molecular chain of sulfonated nanocellulose.
[0208] Figure 3The zeta potential diagram of nanocellulose, sulfonated nanocellulose prepared in this embodiment and quaternary ammonium sulfonated nanocellulose is shown in the figure. It can be seen that the surface charge of nanocellulose is -5.8mV, and the surface charge of sulfonated nanocellulose obtained after sulfonation modification is -11.5mV, which is due to the fact that more anionic sites are combined on the surface of nanocellulose after sulfonation modification. The surface charge of quaternary ammonium sulfonated nanocellulose obtained after quaternary ammonium modification is -2.7mV, which is due to the negative charge on the surface of sulfonated nanocellulose being neutralized by the positive charge of quaternary ammonium salt.
[0209] Figure 4 2 is the XRD diagram of montmorillonite and the intercalated montmorillonite prepared in this embodiment. It can be seen from the figure that the diffraction angle of the (001) plane of the unmodified montmorillonite is 7.1°. According to the Bragg equation 2dsinθ=nλ (wherein, d is the interlayer spacing, θ is the incident angle, λ is the wavelength of the incident X-ray, and n is the diffraction order, which is 1), it can be calculated that the interlayer spacing d of the unmodified montmorillonite is 1.39nm. After the intercalation modification of hexadecyltrimethylammonium bromide and caprolactam, the diffraction peak of the (001) plane of the montmorillonite moves toward the low angle direction. The diffraction angle of the (001) plane of the modified montmorillonite is 4.1°, and the corresponding interlayer spacing is 2.32nm, indicating that hexadecyltrimethylammonium bromide and caprolactam have entered the interlayers of the montmorillonite, thereby causing the interlayer spacing of the montmorillonite to be expanded.
[0210] Figure 5 The infrared spectra of montmorillonite and the intercalated montmorillonite prepared in this example are shown in Figure 1. In the infrared curve of montmorillonite, 3622 cm -1 and 3442cm -1 The corresponding -OH stretching vibration absorption peak is 1164 cm -1 and 1037cm -1 The corresponding stretching vibration absorption peak of Si-O-Si functional group is 1000~500cm -1 The absorption peaks between 1322cm and 1322cm correspond to the internal vibration of Si-O tetrahedron and Al-O octahedron. -1 and 1471cm -1 The 2850cm-1 and 2850cm-2 correspond to the symmetric bending vibration and asymmetric bending vibration absorption peaks of -CH3 in quaternary ammonium salt, respectively. -1 and 2917cm -1 The peaks at 3300cm correspond to the stretching vibration absorption peaks of -CH3 and -CH2- in the quaternary ammonium salt, which indicates that hexadecyltrimethylammonium bromide has been inserted into the interlayer of montmorillonite; -1 The stretching vibration absorption peak of NH corresponding to the amide functional group is 1660 cm -1The C=O stretching vibration absorption peak corresponding to the amide functional group is shown in Figure 2, which indicates that caprolactam has been inserted into the interlayer of montmorillonite.
[0211] Figure 6 and Figure 7 The scanning electron microscope images of the montmorillonite used in this example and the intercalated montmorillonite prepared in this example are shown in FIG. Figure 6 It can be seen that the montmorillonite without intercalation modification has aggregation phenomenon, forming large and unevenly distributed block aggregates. Figure 7 It can be seen that compared with the montmorillonite without intercalation modification treatment, the size of the intercalated montmorillonite obtained after the combined intercalation modification treatment of hexadecyltrimethylammonium bromide and caprolactam is significantly reduced, the dispersibility is significantly improved, and the agglomeration phenomenon is significantly reduced.
[0212] Figure 8 and Fig. 9 They are transmission electron microscope images of the montmorillonite used in this example and the intercalated montmorillonite prepared in this example, Figure 8 It can be seen that the montmorillonite without intercalation modification has densely packed layers, a small interlayer spacing of about 1 nm, and a small lattice fringe spacing and dense arrangement. Fig. 9 It can be seen that compared with the montmorillonite without intercalation modification treatment, the interlayers of the intercalated montmorillonite obtained after the combined intercalation modification treatment of hexadecyltrimethylammonium bromide and caprolactam are stretched, the lattice fringe spacing increases, and the interlayer spacing becomes wider.
[0213] Fig.10 The water contact angle diagrams of montmorillonite, intercalated montmorillonite prepared in this embodiment and composite modified montmorillonite are shown in the figure. It can be seen from the figure that the water contact angle of the unmodified montmorillonite is about 57°, the water contact angle of the intercalated montmorillonite obtained after intercalation modification with hexadecyltrimethylammonium bromide and caprolactam is about 108°, and the water contact angle of the composite modified montmorillonite obtained after hydrophobic modification with a silane coupling agent is about 133°, which indicates that the hydrophobicity of the composite modified montmorillonite obtained after intercalation modification and hydrophobic modification is significantly improved, which is beneficial to improving its compatibility with the polylactic acid matrix.
[0214] Fig.12 and Fig.13 The scanning electron microscope images of the composite modified montmorillonite and the loaded modified montmorillonite prepared in this example are shown in FIG. Fig.12 It can be seen that the composite modified montmorillonite has an ordered layered structure. Fig.13 It can be seen that a large number of titanium dioxide particles and zinc oxide particles are uniformly attached between the layers and on the surface of the loaded modified montmorillonite.
[0215] Fig.14 and Fig.15The transmission electron microscope images of the composite modified montmorillonite and the loaded modified montmorillonite prepared in this example are shown in FIG. Fig.14 It can be seen that the composite modified montmorillonite has a larger interlayer spacing. Fig.15 It can be seen that a large number of titanium dioxide particles and zinc oxide particles are uniformly attached between the layers and on the surface of the loaded modified montmorillonite.
[0216] Example 2
[0217] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0218] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 6 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:52 mL), and ultrasonic dispersion was performed at an ultrasonic power of 320 W for 38 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 52 ° C for 4.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.2 wt %, and the nanocellulose suspension was added. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.142, and the mixture was mixed and stirred at 62°C for 5.8 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 6wt% was dripped into the reaction product to adjust its pH value to 1.8. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 12000Da. After the dialysis was completed, the dialyzed product was placed at -62°C for freeze-drying for 11 hours to obtain sulfonated nanocellulose;
[0219] The sulfonated nanocellulose was added to triethylamine in a ratio of 1 g:32 mL, and then ultrasonically dispersed for 38 min at an ultrasonic power of 320 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.8 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.2, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.22, and mixed and stirred at 62° C. for 3.8 h, and then heating was stopped, and mixed and stirred at room temperature for 13 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 12000 Da, and after the dialysis, the dialyzed product was freeze-dried at -42° C. for 21 h to obtain quaternary ammonium sulfonated nanocellulose;
[0220] (2) dispersing montmorillonite in deionized water to obtain a montmorillonite suspension with a mass fraction of 3 wt%; adding hexadecyltrimethylammonium bromide to the montmorillonite suspension under continuous stirring and heating in a water bath at 72°C, wherein the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:0.35; mixing and stirring for 18 min in a water bath at 72°C; then adding caprolactam, wherein the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is 2.2:1; and mixing and stirring for 3.8 h in a water bath at 72°C; after the reaction is completed, centrifuging at a speed of 7200 rpm for 18 min; washing and drying the precipitate obtained after centrifugation to obtain intercalated montmorillonite;
[0221] The silane coupling agent KH550 and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.2:1, and the mass fraction of the silane coupling agent KH550 in the coupling agent solution is 2wt%; the intercalated montmorillonite is added to the coupling agent solution, the mass ratio of the silane coupling agent KH550 to the intercalated montmorillonite in the coupling agent solution is 0.03:1, the mixture is mixed and stirred at 72° C. for 4.5 hours to react, and after the reaction is completed, the mixture is filtered, washed and dried to obtain a composite modified montmorillonite;
[0222] (3) Tetrabutyl titanate, triethanolamine and anhydrous ethanol are mixed uniformly in a volume ratio of 1:5.2:52 to obtain a titanium precursor solution; zinc acetate, urea, sodium citrate and deionized water are mixed uniformly to obtain a zinc precursor solution, wherein the concentration of zinc acetate in the zinc precursor solution is 6.2 g / L, and the mass ratio of urea, sodium citrate and deionized water is 1:0.22:11; composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water are mixed uniformly to obtain a montmorillonite dispersion, wherein the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 3.5 wt%, and the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water is 3.5:2.2:1;
[0223] Under the conditions of a stirring speed of 720 r / min and a heating temperature of 185°C, a titanium precursor solution was dripped into the montmorillonite dispersion at a dripping rate of 4.5 mL / min, and the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion was 2.1 mL:1 g; after all the titanium precursor solution was dripped, an intermediate solution was obtained, and the same stirring and heating conditions were maintained, and the intermediate solution was continued to be mixed and stirred for 2.8 h; then, under the conditions of a stirring speed of 720 r / min and a heating temperature of 165°C, a titanium precursor solution was dripped at a dripping rate of 4.5 mL / min. A zinc precursor solution is dripped into the intermediate solution, wherein the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is 2.1:1, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 11.5 hours under heating conditions to obtain a composite sol; the composite sol is sequentially aged, centrifuged, washed, dried and calcined to obtain a loaded modified montmorillonite, wherein the aging time is 15 hours, the drying temperature is 62° C., the drying time is 11.5 hours, the calcination temperature is 510° C., and the calcination time is 7.5 hours;
[0224] (4) 81 parts of polylactic acid, 9 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 6 parts of loaded modified montmorillonite obtained in step (3), 2 parts of epoxidized soybean oil, 1.5 parts of paraffin wax and 0.5 parts of antioxidant 1076 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 152° C., the temperature of the second zone is 162° C., the temperature of the third zone is 172° C., the temperature of the fourth zone is 178° C., the temperature of the fifth zone is 186° C., the temperature of the sixth zone is 191° C., the temperature of the seventh zone is 201° C., the temperature of the eighth zone is 196° C., the temperature of the die head is 182° C., and the screw speed is 220 rpm;
[0225] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 178°C, the temperature of the tenth zone is 182°C, the temperature of the eleventh zone is 188°C, the temperature of the twelfth zone is 198°C, and the temperature of the thirteenth zone is 192°C. The screw speed of the film blowing machine is 120rpm, the traction speed of the film blowing machine is 6m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the photocatalytic barrier composite film is obtained.
[0226] Example 3
[0227] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0228] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 7 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:55 mL), and ultrasonically disperse the nanocellulose powder for 35 min at an ultrasonic power of 350 W to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 55 ° C for 4 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4.5 wt %. Add the nanocellulose suspension to the solution. 1,3-propane sultone solution was added, the mass ratio of nanocellulose powder in the nanocellulose suspension to 1,3-propane sultone was 1:0.145, and the mixture was mixed and stirred at 65°C for 5.5 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 7wt% was dripped into the reaction product to adjust its pH value to 1.5. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 15000Da. After the dialysis was completed, the dialyzed product was placed at -65°C for freeze-drying for 10 hours to obtain sulfonated nanocellulose;
[0229] The sulfonated nanocellulose was added to triethylamine in a ratio of 1 g:35 mL, and then ultrasonically dispersed for 35 min at an ultrasonic power of 350 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.5, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.25, and mixed and stirred at 65° C. for 3.5 h, and then heating was stopped, and mixed and stirred at room temperature for 12 h to obtain a reaction product, and then the reaction product was dialyzed for 6 days using a dialysis bag with a molecular weight cutoff of 15000 Da, and after the dialysis, the dialyzed product was freeze-dried at -45° C. for 18 h to obtain quaternary ammonium sulfonated nanocellulose;
[0230] (2) dispersing montmorillonite in deionized water to obtain a montmorillonite suspension with a mass fraction of 3 wt%; adding hexadecyltrimethylammonium bromide to the montmorillonite suspension under continuous stirring and heating in a water bath at 75°C, wherein the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:0.4; mixing and stirring for 15 min in a water bath at 75°C; then adding caprolactam, wherein the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is 2.5:1; and continuing to mix and stir for 3.5 h in a water bath at 75°C. After the reaction is completed, centrifuging at a speed of 7500 rpm for 15 min, washing and drying the precipitate obtained after centrifugation to obtain intercalated montmorillonite;
[0231] The silane coupling agent KH560 and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.5:1, and the mass fraction of the silane coupling agent KH560 in the coupling agent solution is 3wt%; the intercalated montmorillonite is added to the coupling agent solution, the mass ratio of the silane coupling agent KH560 to the intercalated montmorillonite in the coupling agent solution is 0.03:1, the mixture is mixed and stirred at 75°C for 4h to react, and after the reaction is completed, the mixture is filtered, washed and dried to obtain a composite modified montmorillonite;
[0232] (3) Tetrabutyl titanate, triethanolamine and anhydrous ethanol are mixed uniformly in a volume ratio of 1:5.5:55 to obtain a titanium precursor solution; zinc acetate, urea, sodium citrate and deionized water are mixed uniformly to obtain a zinc precursor solution, wherein the concentration of zinc acetate in the zinc precursor solution is 6.5 g / L, and the mass ratio of urea, sodium citrate and deionized water is 1:0.25:12; composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water are mixed uniformly to obtain a montmorillonite dispersion, wherein the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 4wt%, and the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water is 4:2.5:1;
[0233] Under the conditions of a stirring speed of 750 r / min and a heating temperature of 190°C, a titanium precursor solution was dripped into the montmorillonite dispersion at a dripping rate of 5 mL / min, and the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion was 2.2 mL:1 g; after all the titanium precursor solution was dripped, an intermediate solution was obtained, and the same stirring and heating conditions were maintained, and the intermediate solution was continuously mixed and stirred for 2.5 h; then, under the conditions of a stirring speed of 750 r / min and a heating temperature of 170°C, a titanium precursor solution was dripped at a dripping rate of 5 mL / min. A zinc precursor solution is dripped into the intermediate solution at a certain degree, wherein the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is 2.2:1, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 11 hours under heating conditions to obtain a composite sol; the composite sol is sequentially aged, centrifuged, washed, dried and calcined to obtain a loaded modified montmorillonite, wherein the aging time is 18 hours, the drying temperature is 65° C., the drying time is 11 hours, the calcination temperature is 520° C., and the calcination time is 7 hours;
[0234] (4) 82 parts of polylactic acid, 9 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 7 parts of loaded modified montmorillonite obtained in step (3), 1 part of pentaerythritol, 0.8 parts of glyceryl monostearate and 0.2 parts of antioxidant DSTP are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 155° C., the temperature of the second zone is 165° C., the temperature of the third zone is 175° C., the temperature of the fourth zone is 180° C., the temperature of the fifth zone is 187° C., the temperature of the sixth zone is 192° C., the temperature of the seventh zone is 202° C., the temperature of the eighth zone is 197° C., the head temperature is 185° C., and the screw speed is 250 rpm;
[0235] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 180°C, the temperature of the tenth zone is 185°C, the temperature of the eleventh zone is 190°C, the temperature of the twelfth zone is 200°C, and the temperature of the thirteenth zone is 195°C. The screw speed of the film blowing machine is 150rpm, the traction speed of the film blowing machine is 7m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the photocatalytic barrier composite film is obtained.
[0236] Example 4
[0237] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0238] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 8 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:58 mL), and ultrasonic dispersion was performed at an ultrasonic power of 380 W for 32 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 58 ° C for 3.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.8 wt %, and the nanocellulose suspension was added thereto. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.148, the mixture was mixed and stirred at 68°C for 5.2h, and a reaction product was obtained after the reaction was completed. A hydrochloric acid solution with a mass fraction of 8wt% was dripped into the reaction product to adjust the pH value thereof to 1.2, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 18000Da. After the dialysis was completed, the dialyzed product was placed at -68°C for freeze-drying for 8h to obtain sulfonated nanocellulose;
[0239] The sulfonated nanocellulose was added to triethylamine in a ratio of 1 g:38 mL, and then ultrasonically dispersed for 32 min at an ultrasonic power of 380 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.2 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.8, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.28, and mixed and stirred at 68° C. for 3.2 h, and then heating was stopped, and mixed and stirred at room temperature for 11 h to obtain a reaction product, and then the reaction product was dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 18000 Da, and after the dialysis, the dialyzed product was freeze-dried at -48° C. for 15 h to obtain quaternary ammonium sulfonated nanocellulose;
[0240] (2) dispersing montmorillonite in deionized water to obtain a montmorillonite suspension with a mass fraction of 4 wt%; adding hexadecyltrimethylammonium bromide to the montmorillonite suspension under continuous stirring and heating in a water bath at 78°C, wherein the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:0.45; mixing and stirring for 12 min in a water bath at 78°C; then adding caprolactam, wherein the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is 2.8:1; and continuing to mix and stir for 3.2 h in a water bath at 78°C. After the reaction is completed, centrifuging at a speed of 7800 rpm for 12 min, washing and drying the precipitate obtained after centrifugation to obtain intercalated montmorillonite;
[0241] The silane coupling agent KH560 and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.8:1, and the mass fraction of the silane coupling agent KH560 in the coupling agent solution is 4wt%; the intercalated montmorillonite is added to the coupling agent solution, the mass ratio of the silane coupling agent KH560 to the intercalated montmorillonite in the coupling agent solution is 0.04:1, the mixture is mixed and stirred at 78°C for 3.5h to react, and after the reaction is completed, the mixture is filtered, washed and dried to obtain a composite modified montmorillonite;
[0242] (3) Tetrabutyl titanate, triethanolamine and anhydrous ethanol are mixed uniformly in a volume ratio of 1:5.8:58 to obtain a titanium precursor solution; zinc acetate, urea, sodium citrate and deionized water are mixed uniformly to obtain a zinc precursor solution, wherein the concentration of zinc acetate in the zinc precursor solution is 6.8 g / L, and the mass ratio of urea, sodium citrate and deionized water is 1:0.28:13; composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water are mixed uniformly to obtain a montmorillonite dispersion, wherein the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 4.5wt%, and the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water is 4.5:2.8:1;
[0243] Under the conditions of a stirring speed of 780 r / min and a heating temperature of 195°C, a titanium precursor solution was dripped into the montmorillonite dispersion at a dripping rate of 5.5 mL / min, and the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion was 2.3 mL:1 g; after all the titanium precursor solution was dripped, an intermediate solution was obtained, and the same stirring and heating conditions were maintained, and the intermediate solution was continued to be mixed and stirred for 2.2 h; then, under the conditions of a stirring speed of 780 r / min and a heating temperature of 175°C, a titanium precursor solution was dripped at a dripping rate of 5.5 mL / min. A zinc precursor solution is dripped into the intermediate solution, wherein the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is 2.3:1, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 10.5 hours under heating conditions to obtain a composite sol; the composite sol is sequentially aged, centrifuged, washed, dried and calcined to obtain a loaded modified montmorillonite, wherein the aging time is 21 hours, the drying temperature is 68° C., the drying time is 10.5 hours, the calcination temperature is 540° C., and the calcination time is 6.5 hours;
[0244] (4) 83 parts of polylactic acid, 10 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 5 parts of loaded modified montmorillonite obtained in step (3), 1.2 parts of polyvinyl alcohol, 0.5 parts of glyceryl distearate and 0.3 parts of antioxidant 168 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 158°C, the temperature of the second zone is 168°C, the temperature of the third zone is 178°C, the temperature of the fourth zone is 182°C, the temperature of the fifth zone is 188°C, the temperature of the sixth zone is 193°C, the temperature of the seventh zone is 203°C, the temperature of the eighth zone is 198°C, the temperature of the die head is 188°C, and the screw speed is 280 rpm;
[0245] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 182°C, the temperature of the tenth zone is 188°C, the temperature of the eleventh zone is 192°C, the temperature of the twelfth zone is 202°C, and the temperature of the thirteenth zone is 198°C. The screw speed of the film blowing machine is 180rpm, the traction speed of the film blowing machine is 8m / min, and the blowing ratio of the film blowing machine is 4. After film blowing, the photocatalytic barrier composite film is obtained.
[0246] Example 5
[0247] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0248] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 10 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:60 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 400 W for 30 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 60 ° C for 3 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 5 wt %. Add the nanocellulose suspension to the solution. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.15, the mixture was mixed and stirred at 70°C for 5 hours, and a reaction product was obtained after the reaction was completed. A 10wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 1, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 20000Da. After the dialysis was completed, the dialyzed product was placed at -70°C for freeze-drying for 6 hours to obtain sulfonated nanocellulose;
[0249] The sulfonated nanocellulose was added to triethylamine in a ratio of 1 g:40 mL, and then ultrasonically dispersed for 30 min at an ultrasonic power of 400 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 10, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.3, and mixed and stirred at 70° C. for 3 h, and then heating was stopped, and mixed and stirred at room temperature for 10 h to obtain a reaction product, and then the reaction product was dialyzed for 8 days using a dialysis bag with a molecular weight cutoff of 20,000 Da, and after the dialysis, the dialyzed product was freeze-dried at -50° C. for 12 h to obtain quaternary ammonium sulfonated nanocellulose;
[0250] (2) dispersing montmorillonite in deionized water to obtain a montmorillonite suspension with a mass fraction of 5 wt%; adding hexadecyltrimethylammonium bromide to the montmorillonite suspension under continuous stirring and heating in a water bath at 80°C, wherein the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:0.5; mixing and stirring for 10 min in a water bath at 80°C; then adding caprolactam, wherein the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is 3:1; continuing to mix and stir for 3 h in a water bath at 80°C; after the reaction is completed, centrifuging at a speed of 8000 rpm for 10 min; washing and drying the precipitate obtained after centrifugation to obtain intercalated montmorillonite;
[0251] The silane coupling agent KH570 and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 9:1, and the mass fraction of the silane coupling agent KH570 in the coupling agent solution is 5wt%; the intercalated montmorillonite is added to the coupling agent solution, the mass ratio of the silane coupling agent KH570 to the intercalated montmorillonite in the coupling agent solution is 0.05:1, the mixture is mixed and stirred at 80° C. for 3 hours to react, and after the reaction is completed, the mixture is filtered, washed and dried to obtain a composite modified montmorillonite;
[0252] (3) Tetrabutyl titanate, triethanolamine and anhydrous ethanol are mixed uniformly in a volume ratio of 1:6:60 to obtain a titanium precursor solution; zinc acetate, urea, sodium citrate and deionized water are mixed uniformly to obtain a zinc precursor solution, wherein the concentration of zinc acetate in the zinc precursor solution is 7 g / L, and the mass ratio of urea, sodium citrate and deionized water is 1:0.3:15; composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water are mixed uniformly to obtain a montmorillonite dispersion, wherein the mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 5wt%, and the mass ratio of anhydrous ethanol, glacial acetic acid and deionized water is 5:3:1;
[0253] Under the conditions of stirring speed of 800r / min and heating at 200℃, the titanium precursor solution was dripped into the montmorillonite dispersion at a dripping rate of 6mL / min, and the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion was 2.5mL:1g; after all the titanium precursor solution was dripped, an intermediate solution was obtained, and the same stirring and heating conditions were maintained, and the intermediate solution was continued to be mixed and stirred for 2h; then, under the conditions of stirring speed of 800r / min and heating at 180℃, the titanium precursor solution was dripped at a dripping rate of 6mL / min. A zinc precursor solution is dripped into the intermediate solution, wherein the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is 2.5:1, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 10 hours under heating conditions to obtain a composite sol; the composite sol is sequentially aged, centrifuged, washed, dried and calcined to obtain a loaded modified montmorillonite, wherein the aging time is 24 hours, the drying temperature is 70° C., the drying time is 10 hours, the calcination temperature is 550° C., and the calcination time is 6 hours;
[0254] (4) 85 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 5 parts of loaded modified montmorillonite obtained in step (3), 1 part of triacetin, 0.9 parts of zinc stearate and 0.1 parts of antioxidant 691 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 160°C, the temperature of the second zone is 170°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 185°C, the temperature of the fifth zone is 190°C, the temperature of the sixth zone is 195°C, the temperature of the seventh zone is 205°C, the temperature of the eighth zone is 200°C, the temperature of the die head is 190°C, and the screw speed is 300 rpm;
[0255] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 185°C, the temperature of the tenth zone is 190°C, the temperature of the eleventh zone is 195°C, the temperature of the twelfth zone is 205°C, and the temperature of the thirteenth zone is 200°C. The screw speed of the film blowing machine is 200rpm, the traction speed of the film blowing machine is 10m / min, the blowing ratio of the film blowing machine is 5, and the photocatalytic barrier composite film is obtained after film blowing.
[0256] Example 6
[0257] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (2), the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is adjusted to 1.5:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0258] Example 7
[0259] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (2), the mass ratio of hexadecyltrimethylammonium bromide to caprolactam is adjusted to 3.5:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0260] Example 8
[0261] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the heating temperature during the process of dripping the titanium precursor solution is adjusted to 160° C., and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0262] Example 9
[0263] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the heating temperature during the process of dripping the titanium precursor solution is adjusted to 220° C., and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0264] The crystal forms of the supported modified montmorillonite prepared in Example 1, Example 8 and Example 9 were analyzed to obtain the following: Fig.11In the XRD graph shown, the diffraction peaks of anatase titanium dioxide, rutile titanium dioxide and zinc oxide appeared in the XRD curve of the loaded modified montmorillonite prepared in Example 1. However, in the XRD curve of the loaded modified montmorillonite prepared in Example 8, only the diffraction peaks of anatase titanium dioxide and zinc oxide appeared. This is because the low hydrothermal temperature makes the atomic energy insufficient, and it is difficult to overcome the high potential barrier required for the formation of the rutile lattice, resulting in the nucleation of the rutile type being greatly inhibited, so that the finally obtained loaded modified montmorillonite contains only anatase titanium dioxide and zinc oxide. In the XRD curve of the loaded modified montmorillonite prepared in Example 9, only the diffraction peaks of rutile titanium dioxide and zinc oxide appeared. This is because the hydrothermal temperature is high, the atomic diffusion rate increases sharply, the rutile crystals grow rapidly, and the anatase titanium dioxide is completely converted into rutile titanium dioxide, so that the finally obtained loaded modified montmorillonite contains only rutile titanium dioxide and zinc oxide.
[0265] Example 10
[0266] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is adjusted to 1.5 mL:1 g, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0267] Embodiment 11
[0268] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is adjusted to 3 mL:1 g, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0269] Example 12
[0270] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is adjusted to 1.5:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0271] Example 13
[0272] This embodiment provides a method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is adjusted to 3:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0273] Comparative Example
[0274] This comparative example provides a method for preparing a composite film for preserving fruits and vegetables. The difference from Example 1 is that steps (1) to (3) are omitted, quaternary ammonium sulfonated nanocellulose and loaded modified montmorillonite are not added to the mixed material, and the weight proportions of the other components are as follows:
[0275] Polylactic acid 97 parts;
[0276] 1 part of ethylene glycol;
[0277] 1.5 parts of calcium stearate;
[0278] Antioxidant 10100.5 parts;
[0279] Other process parameters and operation steps are exactly the same as those in Example 1.
[0280] Application Examples
[0281] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on green vegetables. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other cartons. Two bunches of green vegetables with similar freshness and the same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The condition of the green vegetables was observed and photographed every two days. Fig.16 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store green vegetables can keep the green vegetables extremely fresh on the 8th day of storage, effectively inhibit the water loss of the green vegetables, maintain the color of the green vegetables, maintain the quality during storage, and extend the shelf life.
[0282] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on mangoes. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other carton. Two mangoes of similar freshness and weight were placed in the two cartons respectively and sealed, and stored at 5°C. The state of the mangoes was observed and photographed every two days, as shown in FIG. Fig.17 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store mangoes can keep the mangoes extremely fresh on the 9th day of storage, effectively inhibit the mangoes from losing water, rotting and deteriorating, maintain their quality during storage, and extend their shelf life.
[0283] The photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the composite films prepared in Examples 1-13 and Comparative Examples were tested, and the testing method was as follows:
[0284] (1) Photocatalytic performance
[0285] The photocatalytic performance of the composite film is characterized by the ethylene degradation rate. The specific test steps are as follows:
[0286] In a dark environment, the composite film provided in Examples 1-13 and the comparative example is laid flat on the bottom of a quartz glass reactor, the reactor is sealed with a quartz cover, 2 mL of ethylene gas is injected into the reactor and stirred for 2 hours to make the ethylene in the reactor and the air evenly mixed to reach the adsorption and desorption equilibrium of the system, 0.3 mL of the mixed gas is extracted from the reactor, and the concentration of ethylene gas in the mixed gas is tested by a gas chromatograph, and the extraction is performed three times and the average value is taken as the initial concentration of ethylene. The composite film in the reactor is irradiated with a 300W, 18A xenon lamp, 0.3 mL of the mixed gas is extracted at fixed time intervals, and the gas chromatograph is used to test to obtain the concentrations of ethylene and carbon dioxide in the mixed gas at that time, the initial concentration of ethylene in the reactor is represented by C0, and the specific concentration of ethylene at a certain moment is represented by C n Indicates that C n The ratio of CO to C0 is the ethylene degradation rate.
[0287] (2) Antibacterial properties
[0288] The antibacterial activity of the composite films provided in Examples 1-13 was analyzed by colony counting method. The composite films provided in Examples 1-13 and the comparative example were cut into 3 mm×3 mm square film samples. 100 μL of 10 6 CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were dispersed on the surface of the film sample and cultured at 37°C for 12 hours to obtain the sample; then 1500μL of PBS solution was used to wash the bacteria from the sample surface, and 20μL of PBS solution was taken and dispersed on the nutrient agar plate, and cultured at 37°C for 12 hours, after which the surviving colonies were counted. The antibacterial rate (%) was calculated using the following formula:
[0289]
[0290] Wherein, X is the number of colonies on the composite film sample provided in the comparative example, and Y is the number of colonies on the composite film sample provided in Examples 1-13.
[0291] (3) Barrier properties
[0292] The barrier properties of the composite films provided in Examples 1-13 and the comparative examples were characterized by water vapor permeability. The water vapor permeability was measured in a constant temperature and humidity chamber according to GB / T 1037-2021 “Determination of Water Vapor Permeability of Plastic Films and Sheets by Cup Weight Gain and Weight Loss Method”. The experimental conditions were: temperature 38±0.6°C, relative humidity 90%±2%.
[0293] (4) Mechanical properties
[0294] The mechanical properties of the composite films were characterized by tensile strength and elongation at break. The tensile strength and elongation at break of the composite films provided in Examples 1 to 13 and the comparative example were measured using a tensile testing machine, and the tensile rate was set to 50 mm / min.
[0295] The test data is shown in Table 1.
[0296] Table 1
[0297]
[0298] It can be seen from the test data provided in Table 1 that the composite films provided in Examples 1-5 of the present invention have excellent photocatalytic properties, antibacterial properties, barrier properties and mechanical properties.
[0299] It can be seen from the test data of Example 1, Example 6 and Example 7 that too high or too low a dosage of hexadecyltrimethylammonium bromide will directly affect the intercalation modification effect of montmorillonite, thereby affecting the subsequent loading effect of titanium dioxide and zinc oxide, and ultimately affecting the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the composite film.
[0300] It can be seen from the test data of Example 1, Example 8 and Example 9 that too high or too low heating temperature during the process of adding the titanium precursor solution will directly affect the crystal form of titanium dioxide, and ultimately affect the photocatalytic performance and antibacterial performance of the composite film.
[0301] It can be seen from the test data of Example 1, Example 10 and Example 11 that excessive or insufficient dosage of tetrabutyl titanate directly affects the loading amount and crystal form of titanium dioxide in the loaded modified montmorillonite, and ultimately affects the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the composite film.
[0302] It can be seen from the test data of Example 1, Example 12 and Example 13 that excessive or insufficient dosage of zinc acetate directly affects the loading amount of zinc oxide in the loaded modified montmorillonite, and ultimately affects the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the composite film.
[0303] It can be seen from the test data of Example 1 and the comparative example that the present invention can significantly improve the photocatalytic performance, antibacterial performance, barrier performance and mechanical properties of the polylactic acid composite film by adding quaternary ammonium sulfonated nanocellulose and loaded modified montmorillonite to the composite film.
[0304] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a photocatalytic barrier composite film for preserving fruits and vegetables, characterized in that: The preparation method comprises: (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose; (II) using hexadecyltrimethylammonium bromide and caprolactam to carry out organic intercalation modification on montmorillonite to obtain intercalated montmorillonite; then, using a silane coupling agent to carry out hydrophobic modification on the intercalated montmorillonite to obtain a composite modified montmorillonite; (III) uniformly mixing tetrabutyl titanate, triethanolamine and anhydrous ethanol to obtain a titanium precursor solution; uniformly mixing zinc acetate, urea, sodium citrate and deionized water to obtain a zinc precursor solution; uniformly mixing the composite modified montmorillonite, anhydrous ethanol, glacial acetic acid and deionized water to obtain a montmorillonite dispersion; under stirring and heating conditions, sequentially dropping the titanium precursor solution and the zinc precursor solution into the montmorillonite dispersion to obtain a composite sol; sequentially aging, centrifuging, washing, drying and calcining the composite sol to obtain a loaded modified montmorillonite; (IV) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the loaded modified montmorillonite obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the photocatalytic barrier composite film for preserving fruits and vegetables.
2. The preparation method according to claim 1, characterized in that: In step (I), the sulfonated nanocellulose is prepared by the following method: The nanocellulose powder is added to a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added to the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, a hydrochloric acid solution is dripped into the reaction product to adjust the pH value thereof, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose; The mass fraction of the sodium hydroxide solution is 5-10wt%; The ratio of the nanocellulose powder to the sodium hydroxide solution is 1 g: (50-60) mL; The ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400W; The ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 minutes; The mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours; The heating temperature of the nanocellulose dispersion during mixing and stirring is 50-60°C; The 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide; The mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%; The mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14-0.15); The mixing and stirring time of the nanocellulose suspension and 1,3-propane sultone is 5 to 6 hours; The heating temperature when the nanocellulose suspension and 1,3-propane sultone are mixed and stirred is 60-70°C; The mass fraction of the hydrochloric acid solution is 5-10wt%; Adding hydrochloric acid solution dropwise into the reaction product to adjust the pH value thereof to 1-2; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 2 to 3 days; The freeze drying temperature is -60 to -70°C; The freeze-drying time is 6 to 12 hours.
3. The preparation method according to claim 1, characterized in that: In step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method: The sulfonated nanocellulose is added to triethylamine to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, octadecyltrimethylammonium chloride is then added to the sulfonated nanocellulose suspension, mixed and stirred, and heated for a period of time, then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose; The ratio of the sulfonated nanocellulose to triethylamine is 1 g: (30-40) mL; The ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and triethylamine is 300-400W; The ultrasonic dispersion time of the sulfonated nanocellulose and triethylamine is 30 to 40 minutes; The concentration of the alkali solution is 0.5-1.5 mol / L; Adding alkaline solution dropwise to the sulfonated nanocellulose suspension to adjust the pH value thereof to 9-10; The mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2-0.3); The mixing time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride is 3 to 4 hours; The heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred is 60-70°C; The mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 5 to 8 days; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 12 to 24 hours.
4. The preparation method according to claim 1, characterized in that: In step (II), the intercalated montmorillonite is prepared by the following method: Dispersing montmorillonite in deionized water to obtain a montmorillonite suspension; adding hexadecyltrimethylammonium bromide and caprolactam to the montmorillonite suspension in sequence under continuous stirring and water bath heating conditions to react, centrifuging after the reaction, washing and drying the precipitate obtained after the centrifugation to obtain the intercalated montmorillonite; The mass fraction of montmorillonite in the montmorillonite suspension is 2-5wt%; The mass ratio of montmorillonite to hexadecyltrimethylammonium bromide in the montmorillonite suspension is 1:(0.3-0.5); The mass ratio of hexadecyltrimethylammonium bromide to caprolactam is (2-3):1; The water bath heating temperature is 70-80°C; After adding hexadecyltrimethylammonium bromide to the montmorillonite suspension, continue mixing and stirring under heating in a water bath for 10 to 20 minutes, and then add caprolactam; After adding caprolactam, continue mixing and stirring under heating in a water bath for 3 to 4 hours; The centrifugal speed is 7000-8000 rpm; The centrifugation time is 10 to 20 minutes.
5. The preparation method according to claim 1, characterized in that: In step (II), the composite modified montmorillonite is prepared by the following method: The silane coupling agent and the ethanol aqueous solution are uniformly mixed to obtain a coupling agent solution, the intercalated montmorillonite is added to the coupling agent solution, mixed and stirred, and heated to react, and after the reaction is completed, filtered, washed, and dried to obtain the composite modified montmorillonite; The volume ratio of ethanol to deionized water in the ethanol aqueous solution is (8-9):1; The mass fraction of the silane coupling agent in the coupling agent solution is 1-5wt%; The mass ratio of the silane coupling agent in the coupling agent solution to the intercalated montmorillonite is (0.02-0.05):1; The reaction temperature of the intercalated montmorillonite and the coupling agent solution is 70-80°C; The reaction time of the intercalated montmorillonite and the coupling agent solution is 3 to 5 hours.
6. The preparation method according to claim 1, characterized in that: In step (III), the volume ratio of tetrabutyl titanate, triethanolamine and anhydrous ethanol is 1:(5-6):(50-60); The concentration of zinc acetate in the zinc precursor solution is 6-7 g / L; The mass ratio of urea, sodium citrate and deionized water in the zinc precursor solution is 1:(0.2-0.3):(10-15); The mass fraction of the composite modified montmorillonite in the montmorillonite dispersion is 3-5wt%; The mass ratio of anhydrous ethanol, glacial acetic acid and deionized water in the montmorillonite dispersion is (3-5):(2-3):1; The ratio of tetrabutyl titanate in the titanium precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is (2-2.5) mL:1 g; The mass ratio of zinc acetate in the zinc precursor solution to the composite modified montmorillonite in the montmorillonite dispersion is (2-2.5):1; The specific process of dripping the titanium precursor solution and the zinc precursor solution is as follows: Under stirring and heating conditions, first, the titanium precursor solution is dripped into the montmorillonite dispersion, and after all the titanium precursor solution is dripped, an intermediate solution is obtained, and the intermediate solution is continuously mixed and stirred for 2 to 3 hours under heating conditions; Subsequently, the zinc precursor solution is dripped into the intermediate solution under stirring and heating conditions, and after all the zinc precursor solution is dripped, a reaction solution is obtained, and the reaction solution is continuously mixed and stirred for 10 to 12 hours under heating conditions to obtain the composite sol; The heating temperature during the process of dropwise adding the titanium precursor solution is 180-200° C.; The stirring speed during the process of dropwise adding the titanium precursor solution is 700-800 r / min; The titanium precursor solution is dripped at a rate of 4-6 mL / min; The heating temperature during the process of dropwise adding the zinc precursor solution is 160-180° C.; The stirring speed during the process of dropwise adding the zinc precursor solution is 700-800 r / min; The zinc precursor solution is dripped at a rate of 4-6 mL / min; The aging time is 12 to 24 hours; The drying temperature is 60-70°C; The drying time is 10 to 12 hours; The calcination temperature is 500-550°C; The calcination time is 6 to 8 hours.
7. The preparation method according to claim 1, characterized in that: In step (IV), the weight proportions of the components in the mixed material are as follows: Polylactic acid 80-85 parts; 8-10 parts of quaternary ammonium sulfonated nanocellulose; Loading modified montmorillonite 5-8 parts; 1~2 parts of plasticizer; 0.5~1.5 parts of lubricant; Antioxidant 0.1~0.5 parts; The plasticizer includes any one of triacetin, tributyl sodium citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, tributyl sodium acetyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof; The lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof; The antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.
8. The preparation method according to claim 1, characterized in that: In step (IV), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction; The temperature of the first zone is 150-160°C; The temperature of the second zone is 160-170°C; The temperature of the third zone is 170-180°C; The temperature of the fourth zone is 175-185°C; The temperature of the fifth zone is 185-190°C; The temperature of the sixth zone is 190-195°C; The temperature of the seventh zone is 200-205°C; The temperature of the eighth zone is 195-200°C; The head temperature of the screw extruder is 180-190°C; The screw speed of the screw extruder is 200-300 rpm.
9. The preparation method according to claim 1, characterized in that: In step (IV), the film blowing process is carried out in a film blowing machine, and the inside of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction; The temperature of the ninth zone is 175-185°C; The temperature of the tenth zone is 180-190°C; The temperature of the eleventh zone is 185-195°C; The temperature of the twelfth zone is 195-205°C; The temperature of the thirteenth zone is 190-200°C; The screw speed of the film blowing machine is 100-200 rpm; The traction speed of the film blowing machine is 5-10 m / min; The blowing ratio of the film blowing machine is 2-5.
10. A photocatalytic barrier composite film for preserving fruits and vegetables prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The photocatalytic barrier composite film for preserving fruits and vegetables comprises polylactic acid, quaternary ammonium sulfonated nanocellulose, loaded modified montmorillonite, a plasticizer, a lubricant and an antioxidant.
Citation Information
Cited By
Antibacterial antifouling polymer composite material as well as preparation method and application thereof
CN122213673A